A chlorophyll halo over maud rise in the southern ocean - Ducrocq, Bertrand; Steiger, Nadine; du Plessis, Marcel; Sallée, Jean-Baptiste; Moreau, Sébastien; Swart, Sebastiaan (Nature communications, 2025)
Phytoplankton blooms above the seamount Maud Rise in the Antarctic Ocean have been reported but their emerging mechanisms and their importance for the wider Southern Ocean are not well known. We use satellite data spanning over the last two  decades and in-situ data collected from a ship, an underwater glider and Biogeochemical-Argo profiling floats to understand the processes involved in the formation of Maud Rise phytoplankton blooms. We find that the seamount generates upwelling of warm deep water that transports heat, and likely dissolved iron, to the surface via diapycnal mixing. This creates a recurring annular structure of chlorophyll concentration (or chlorophyll halo) in correspondence with the previously observed warm water and sea ice halo over Maud Rise. The in-situ observations reveal integrated chlorophyll-a concentrations of up to 100 mg·m(-2), which suggests exceptionally high phytoplankton biomass within the Southern Ocean, thus making the seamount a regional phytoplankton hotspot.
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; marin biologi; oseanografi

Unmanned Aerial Vehicles for Real-Time Vegetation Monitoring in Antarctica: A Review - Lockhart, Kaelan; Sandino, Juan; Amarasingam, Narmilan; Hann, Richard; Bollard, Barbara; Gonzalez, Felipe (Remote Sensing, 2025)
The unique challenges of polar ecosystems, coupled with the necessity for high-precision data, make Unmanned Aerial Vehicles (UAVs) an ideal tool for vegetation monitoring and conservation studies in Antarctica. This review draws on existing studies on Antarctic UAV vegetation mapping, focusing on their methodologies, including surveyed locations, flight guidelines, UAV specifications, sensor technologies, data processing techniques, and the use of vegetation indices. Despite the potential of established Machine-Learning (ML) classifiers such as Random Forest, K Nearest Neighbour, and Support Vector Machine, and gradient boosting in the semantic segmentation of UAV-captured images, there is a notable scarcity of research employing Deep Learning (DL) models in these extreme environments. While initial studies suggest that DL models could match or surpass the performance of established classifiers, even on small datasets, the integration of these advanced models into real-time navigation systems on UAVs remains underexplored. This paper evaluates the feasibility of deploying UAVs equipped with adaptive path-planning and real-time semantic segmentation capabilities, which could significantly enhance the efficiency and safety of mapping missions in Antarctica. This review discusses the technological and logistical constraints observed in previous studies and proposes directions for future research to optimise autonomous drone operations in harsh polar conditions.
Keywords: Antarktis; droner; dyp læring; fjernmåling; kartlegging; kunstig intelligens (KI); kybernetikk; maskinlæring; teknologi; vegetasjon

Shackletons svanesang, Shackleton-Rowett-ekspedisjonen 1921-22 - Chojecki, Jan (Polarboken, 2024)
Keywords: Sørishavet; ekspedisjoner; historie

Mineralogical and Geochemical Response to Fluid Infiltration into Cambrian Orthopyroxene-Bearing Granitoids and Gneisses, Dronning Maud Land, Antarctica - Engvik, Ane K.; Corfu, Fernando; Kleinhanns, Ilka C.; Taubald, Heinrich; Elvevold, Synnøve (Minerals, 2024)
Fluid infiltration into Proterozoic and Early Palaeozoic dry, orthopyroxene-bearing granitoids and gneisses in Dronning Maud Land, Antarctica, has caused changes to rock appearance, mineralogy, and rock chemistry. The main mineralogical changes are the replacement of orthopyroxene by hornblende and biotite, ilmenite by titanite, and various changes in feldspar structure and composition. Geochemically, these processes resulted in general gains of Si, mostly of Al, and marginally of K and Na but losses of Fe, Mg, Ti, Ca, and P. The isotopic oxygen composition (δ18OSMOW = 6.0‰–9.9‰) is in accordance with that of the magmatic precursor, both for the host rock and infiltrating fluid. U-Pb isotopes in zircon of the altered and unaltered syenite to quartz-monzonite indicate a primary crystallization age of 520.2 ± 1.0 Ma, while titanite defines alteration at 485.5 ± 1.4 Ma. Two sets of gneiss samples yield a Rb-Sr age of 517 ± 6 Ma and a Sm-Nd age of 536 ± 23 Ma. The initial Sr and Nd isotopic ratios suggest derivation of the gneisses from a relatively juvenile source but with a very strong metasomatic effect that introduced radiogenic Sr into the system. The granitoid data indicate instead a derivation from Mid-Proterozoic crust, probably with additions of mantle components.
Keywords: Dronning Maud Land; NARE 1996/97; geokjemi; geokronologi; geologi; mineralogi

Historical occurrence of Antarctic icebergs within mercantile shipping routes and the exceptional events of the 1890s - Headland, Robert Keith; Hughes, Nicholas Edward; Wilkinson, Jeremy Paul (Journal of Glaciology, 2023)
A major consideration for maritime activity in the Southern Hemisphere is the northern limit of icebergs, or the Southern Ocean Limit Of Known Ice (SOLOKI). This analysis of historical reports of icebergs during Southern Hemisphere voyages from 1687 to 1933 provides a basis for examination of their geographical and chronological occurrence during ~250 years. The analyses use tabulated data from 742 voyages and other reports from many sources, some including first-person descriptions. While these data are dependent on icebergs being reported by mariners, as well as the variable frequency of voyages, they demonstrate distinct periods of exceptional frequency of icebergs occurring in certain localities, particularly the far South Atlantic. Based upon historical records the evidence suggests unprecedented numbers of icebergs were present in southern shipping channels in the 1890s. When these historical observations are combined with modern iceberg drift trajectories, their possible origin can be elucidated. Owing to the numbers of icebergs seen and their geographical spread, our results suggest that this was possibly the largest near-synchronous calvings in the last 300 years, and the northernmost extent of the SOLOKI.
Keywords: Sørishavet; glasiologi; isfjell

The Antarctic Peninsula: Argentina and Chile in the era of global change - Vidal, Florian (The Polar Journal, 2023)
While Argentine-Chilean relations have long been swayed between cooperation and confrontation since their independence in the 19th century and a long-standing presence in Antarctica, the stretch between Tierra del Fuego to the Antarctic Peninsula stands as the closest lane (i.e. about 1,000 km) to any other continent. Despite their territorial dispute over islands on the fractured southern tip of South America and territorial claims on the Antarctic, their common diplo-matic ground successfully defuses any potential geopolitical instability. Along with Chile and Argentina, British claims overlap in the Antarctic Peninsula, which establishes unique geopolitical conditions in the whole of Antarctica. In this context, scientific missions and growing tourist activities could transform the region into the Antarctic gateway. From potential mineral resources exploitation to the United States- China global competition, the South Atlantic area could become a strategic bridgehead in light of the brewing geopolitical shift during the 21st century. Considering that climate change and geostrategic conditions evolve somewhat quickly to transform the Western Antarctic area, this article aims to assess and comprehend how these external drivers may affect the two South American countries. Given the fact that Antarctica is part of their respective national narrative, how do Argentina and Chile intend to maintain their presence and protect their interest in these shifting conditions? What are the vectors for partnering with the world’s great powers, such as China? Ultimately, could this space become a choke point through the 21st century?
Keywords: Antarktis; geopolitikk; politikk; ressurser

Utryddelsen : historien om den norske industrielle hvalfangsten - Ytreberg, Espen (Press, 2023)
Det var det første norske oljeeventyret. I dag snakker ingen om det. I drøye hundre år etter at Svend Foyn oppfant granatharpunen i 1863, var Norge pådriver, innovatør og profitør i den største nedslaktingen av ville dyr verden noensinne har sett: Den globale industrielle hvalfangsten. Norge utviklet teknologi, åpnet nye fangstfelt og arbeidet internasjonalt for å hindre regulering og begrensninger. Da hvalfangstens epoke var over, var nesten ingen igjen av hvalene som hadde fylt verdenshavene. I dypet rådet en ny stillhet. Langs strendene i Sørishavet lå bare de råtnende hvalskrottene igjen. Men de norske hvalfangstrederne hadde blitt rike. Vanlige norske arbeidere bemannet den norske hvalfangstindustriens hvalkokerier og hvalbåter. For disse mennene var arbeidet slit, eventyr og mareritt. Etter dem finnes et stort materiale - fotografier, dagbøker, brev - som forteller om arbeidernes erfaringer fra slaktesonene i Sørishavet. I Utryddelsen forteller Espen Ytreberg historien om den norske hvalfangsten fra arbeidernes perspektiv. Han tar oss med på fangsten, lar oss følge arbeidernes opplevelser, setter bildene og beretningene deres inn i en større historisk sammenheng. Utryddelsen er et enestående stykke historieskriving om et avgjørende kapittel i norsk historie - en bok som åpner den nære norske fortiden opp for oss på helt nye måter.
Keywords: Sørishavet; hvalfangst

South American claims in Antarctica: colonial, malgre tout - Mancilla, A (POLAR JOURNAL, 2022)
Argentina and Chile, known in the world of Antarctic politics as the 'South American claimants', have shown themselves since the inception of their interests in the White Continent as standing alone and in opposition to the advances of the colonial powers of the North - especially the United Kingdom. As Shirley Scott has suggested, while the UK was busy staking claims over Antarctica and treating it as terra nullius, Argentina and Chile ascertained what they took to be their historical rights to the continent, inherited from the time when they were Spanish colonies. In this article, I support Argentina's and Chile's contention that the attitude and procedure followed by the other claimants to the continent was unequivocally colonial, but I reject their contention that theirs was not. I examine four sites where their colonial spirit is revealed: their use of the geographic doctrines of continuity and contiguity, and of the sector principle; the appeal to historic rights inherited from the time when they were Spanish colonies; their expansion to Antarctica through the establishment of military settlements, and their underlying economic and strategic interests, no different from their 'Northern' counterparts. I then point to some specific and general implications of reinterpreting their story in this light.
Keywords: Antarktis; politikk

Isolation, Physiological Characterization, and Antibiotic Susceptibility Testing of Fast-Growing Bacteria from the Sea-Affected Temporary Meltwater Ponds in the Thala Hills Oasis (Enderby Land, East Antarctica) - Akulava, Volha; Miamin, Uladzislau; Akhremchuk, Katsiaryna; Valentovich, Leonid; Dolgikh, Andrey; Shapaval, Volha (Biology, 2022)
In this study, for the first time, we report the identification and characterization of culturable fast-growing bacteria isolated from the sea-affected temporary meltwater ponds (MPs) in the East Antarctica area of the Vecherny region (−67.656317, 46.175058) of the Thala Hills Oasis, Enderby Land. Water samples from the studied MPs showed alkaline pH (from 8.0 to 10.1) and highly varied total dissolved solids (86–94,000 mg/L). In total, twenty-nine bacterial isolates were retrieved from the studied MPs. The phylogenetic analysis based on 16S rRNA gene sequence similarities showed that the isolated bacteria belong to the phyla Proteobacteria, Actinobacteria, Firmicutes, and Bacteroidetes and the twelve genera Pseudomonas, Shewanella, Acinetobacter, Sporosarcina, Facklamia, Carnobacterium, Arthrobacter, Brachybacterium, Micrococcus, Agrococcus, Leifsonia, and Flavobacterium. Most of the isolated bacteria were psychrotrophs and showed the production of one or more extracellular enzymes. Lipolytic and proteolytic activities were more prevalent among the isolates. Five isolates from the Actinobacteria phylum and one isolate from the Bacteroidetes phylum had strong pigmentation. Antibiotic susceptibility testing revealed that most of the isolates are resistant to at least one antibiotic, and seven isolates showed multi-resistance.
Keywords: Antarktis; bakterier; biokjemi

Oppdagelsen av Shackletons Endurance: fremtidig beskyttelse eller plyndring? / av redaksjonen - Barr, Susan; Gjertz, Ian; Mehlum, Fridtjof (Polarboken, 2022)
Kunngjøringen 9. mars 2022 om oppdagelsen av Ernest Shackletons skip Endurance vekket omfattende interesse. Skipet står oppreist på kjølen rundt 3000 meter under stedet der det i 1915 ble presset ned under trykket av den antarktiske isen. Vraket synes å være i forbausende god stand. Medieomtaler indikerer at det faktum at vrakområdet er anerkjent somet fredet kulturminne under Antarktistraktaten gjorde at ingenting ble rørt eller fjernet. Det ble kun fotodokumentert fra passende avstand. Denne ansvarsfulle tilnærmingen må berømmes.
Keywords: Endurance (skip); Sørishavet; kulturminner

På jobb - lang borte fra kontoret - blant spektakulære fjell og landskap - Elvevold, Synnøve (Polarboken, 2022)
Keywords: Dronning Maud Land; geologi

Three-decade spatial patterns in surface mass balance of the Nivlisen Ice Shelf, central Dronning Maud Land, East Antarctica - Pratap, Bhanu; Dey, Rahul; Matsuoka, Kenichi; Moholdt, Geir; Lindbäck, Katrin; Goel, Vikram; Laluraj, C M; Thamban, Meloth (Journal of Glaciology, 2022)
The coastal Droning Maud Land in East Antarctica is characterized by small ice shelves with numbers of promontories and locally grounded isles, both called ice rises. These ice rises are typically dome-shaped and surface elevations are hundreds of meters above the surrounding ice shelves, which cause strong orographic effects on surface mass balance (SMB). We conducted shallow ice-penetrating radar sounding to visualize firn stratigraphy in the top 35 m over ~400 km of profiles across the Nivlisen Ice Shelf, and in a grid pattern over two adjacent ice rises (Djupranen and Leningradkollen). We tracked six reflectors (isochrones) and dated them using two ice cores taken at the ice rise summits, from which SMB over six periods in the past three decades was retrieved. The overall SMB pattern across the ice shelf remained similar for all periods; however, the eastwest contrast in SMB varies by a factor of 1.5–2 between the Leningradkollen and Djupranen grounding lines. The SMB patterns over the ice rises are more varied owing to complex interactions between topography, snowfall and wind. We use our results to evaluate the regional climate model RACMO2.3p2 in terms of the spatial SMB distribution and temporal changes over the ice shelf and ice rises at regional scale.
Keywords: Dronning Maud Land; glasiologi; isshelf; stratigrafi

Temperature- and Nutrients-Induced Phenotypic Changes of Antarctic Green Snow Bacteria Probed by High-Throughput FTIR Spectroscopy - Smirnova, Margarita; Tafintseva, Valeria; Kohler, Achim; Miamin, Uladzislau; Shapaval, Volha (Biology, 2022)
Temperature fluctuations and nutrient composition are the main parameters influencing green snow microbiome. In this study we investigated the influence of temperature and nutrient conditions on the growth and cellular chemical profile of bacteria isolated from green snow. Chemical profiling of the green snow bacteria was done by high-throughput FTIR spectroscopy combined with multivariate data analysis. We showed that temperature and nutrients fluctuations strongly affect growth ability and chemical profile of the green snow bacteria. The size of colonies for green snow bacteria grown at higher (25 °C) and lower (4 °C and 10 °C) than optimal temperature (18 °C) was smaller. All isolates grew on rich medium, and only 19 isolates were able to grow on synthetic minimal media. Lipid and mixed spectral regions showed to be phylogeny related. FTIR fingerprinting indicates that lipids are often affected by the temperature fluctuations. Growth on different media resulted in the change of the whole chemical profile, where lipids showed to be more affected than proteins and polysaccharides. Correlation analysis showed that nutrient composition is clearly strongly influencing chemical changes in the cells, followed by temperature.
Keywords: Antarktis; bakterier; kjemi; mikrobiologi; multivariate data analysis

International Polar and Geophysical Years - Barr, Susan (Antarctic Resolution, 2021)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Det internasjonale polaråret (IPY); forskning; internasjonal samarbeid

Roald Amundsens's Tent at the South Pole - Barr, Susan (Antarctic Resolution, 2021)
Keywords: Antarktis; Norge; Roald Amundsen; Sydpolsekspedisjonen; historie

The Precursor of the International Geophysical Year. The Norwegian-British-Swedish Antarctic Expedition - Domaas, Christel Misund (Antarctic Resolution, 2021)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Geological map of Jutulsessen (Dronning Maud Land) - Elvevold, Synnøve; Engvik, A K; Hansen, C; Jacobs, J; Meiklejohn, I; Myhre, P I; Rudolph, E (Norsk Polarinstitutt, 2021)
Keywords: Dronning Maud Land; geologi; kart

Dronning Maud Land: der ingen skulle tru at det var fjell ... - Engeland, Sveinung; Engeland, Sveinung (Høyde over havet : hvordan fjellene våre ble målt og satt på kartet, 2021)
Keywords: Dronning Maud Land; ekspedisjoner; geografi; kartlegging; oppdagelsesreiser

Decolonising Antarctica - Mancilla, Alejandra (Philosophies of polar law, 2021)
Keywords: Antarktis; Antarktistraktaten; internasjonal politikk; polarområdene; rettsfilosofi

Maudheimexpeditionen/NSBX 1949-1952 - Norén, Karl-Gunnar (Polarexpeditionernas proviant: 1872-1949, 2021)
Keywords: Antarktis; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ernæring

Roald Amundsens Sydpolsexpedition 1909-1912 - Norén, Karl-Gunnar (Polarexpeditionernas proviant: 1872-1949, 2021)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ernæring; oppdagelsesreiser

Icebreaking polar class research vessels: New Antarctic fleet capabilities - Rogan-Finnemore, Michelle; Ojeda, Miguel; Paz Acosta, Jorge Manuel; Bretel, Patrice; Browne, Nick; Flått, Stig; Shuoren, Wang; Sliester, Randolph (Polar Record, 2021)
Supporting Antarctic scientific investigation is the job of the national Antarctic programmes, the government entities charged with delivering their countries’ Antarctic research strategies. This requires sustained investment in people, innovative technologies, Antarctic infrastructures, and vessels with icebreaking capabilities. The recent endorsement of the International Maritime Organization (IMO) Polar Code (2015) means that countries must address challenges related to an ageing icebreaking vessel fleet. Many countries have recently invested in and begun, or completed, builds on new icebreaking Polar research vessels. These vessels incorporate innovative technologies to increase fuel efficiency, to reduce noise output, and to address ways to protect the Antarctic environment in their design. This paper is a result of a Council of Managers of National Antarctic Programs (COMNAP) project on new vessel builds which began in 2018. It considers the recent vessel builds of Australia’s RSV Nuyina, China’s MV Xue Long 2, France’s L’Astrolabe, Norway’s RV Kronprins Haakon, Peru’s BAP Carrasco, and the United Kingdom’s RRS Sir David Attenborough. The paper provides examples of purposeful consideration of science support requirements and environmental sustainability in vessel designs and operations.
Keywords: Sørishavet; skipsfart; teknologi

Last glacial cycle ice surface variations in western Dronning Maud Land, East Antarctica - Sirevaag, Hallgeir; Ksienzyk, Anna Katharina; Jacobs, Joachim (Norsk Geologisk Forening (NGF), 2021)
The East Antarctic Ice Sheet (EAIS) is generally assumed to have been relatively insensitive to Quaternary climate change. However, recent studies have shown potential instabilities in coastal, marine sectors of the EAIS. In addition, long-term climate reconstructions and modelling experiments indicate the potential for significant changes in ice volume and ice sheet configuration since the Pliocene. Hence, more empirical evidence for ice surface and ice volume changes is required to discriminate between contrasting inferences. MAGIC-DML is an ongoing Swedish-US-Norwegian-German-UK collaboration focused on improving ice sheet models by filling critical data gaps that exist in our knowledge of the timing and pattern of ice surface changes along the western Dronning Maud Land (DML) margin and combining this with advances in numerical techniques. Here, we report cosmogenic multi-nuclide data from bedrock and erratics at 72 sample locations on nunatak ranges from Heimefrontfjella to along Penck-Jutulstraumen ice stream throughs in western Dronning Maud Land. The sample locations span elevations between 741-2437 m above sea level, and record apparent exposure ages between <2 ka and >5 Ma. The highest bedrock samples, from high on the inland nunatak ranges, indicate continuous exposure since >5 Ma, with a very low erosion rate of 15±3 cm Ma-1. These results indicate that the ice sheet has not extensively buried and eroded these mountain ranges since at least the Pliocene Moreover, and in contrast to current studies in eastern Dronning Maud Land, we record clear indications of a thicker-than-present ice sheet along the Penck-Jutulstraumen throughs within the last glacial cycle, with a thinning of ~35-120 m towards the present ice surface on several nunataks during the Holocene (~2-11 ka). These results thus indicate ice-surface fluctuations of several hundred meters between the current grounding line and the edge of the polar plateau for the last glacial cycle.
Keywords: Dronning Maud Land; geologi

The return of the South Pole sled dogs : with Amundsen’s and Mawson’s antarctic expeditions - Tahan, Mary R. (Springer Nature, 2021)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; sledehunder; trekkhunder

Antarktis jubilerer (Polarboken, 2020)
Keywords: Antarktis; historie

Från kallt till varmt - norsk oceanografisk forskning i Weddelhavet, Antarktis - Darelius, Elin Maria K; Foldvik, Arne (Det norske videnskaps-akademi, 2020)
Keywords: Sørishavet; Weddellhavet; oseanografi

Characteristics of ice rises and ice rumples in Dronning Maud Land and Enderby Land, Antarctica - Goel, Vikram; Matsuoka, Kenichi; Berger, Cesar Deschamps; Lee, Ian; Dall, Jørgen; Forsberg, René (Journal of Glaciology, 2020)
Ice rises and rumples, locally grounded features adjacent to ice shelves, are relatively small yet play significant roles in Antarctic ice dynamics. Their roles generally depend upon their location within the ice shelf and the stage of the ice-sheet retreat or advance. Large, long-stable ice rises can be excellent sites for deep ice coring and paleoclimate study of the Antarctic coast and the Southern Ocean, while small ice rises tend to respond more promptly and can be used to reveal recent changes in regional mass balance. The coasts of Dronning Maud Land (DML) and Enderby Land in East Antarctica are abundant with these features. Here we review existing knowledge, presenting an up-to-date status of research in these regions with focus on ice rises and rumples. We use regional datasets (satellite imagery, surface mass balance and ice thickness) to analyze the extent and surface morphology of ice shelves and characteristic timescales of ice rises. We find that large parts of DML have been changing over the past several millennia. Based on our findings, we highlight ice rises suitable for drilling ice cores for paleoclimate studies as well as ice rises suitable for deciphering ice dynamics and evolution in the region.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; glasiologi; isshelf

High-resolution distributed vertical strain and velocity from repeat borehole logging by optical televiewer: Derwael Ice Rise, Antarctica - Hubbard, Bryn; Philippe, Morgane; Pattyn, Frank; Drews, Reinhard; Young, Tun Jan; Bruyninx, Carine; Bergeot, Nicolas; Fjøsne, Karen; Tison, Jean-Louis (Journal of Glaciology, 2020)
Direct measurements of spatially distributed vertical strain within ice masses are scientifically valuable but challenging to acquire. We use manual marker tracking and automatic cross correlation between two repeat optical televiewer (OPTV) images of an ~100 m-long borehole at Derwael Ice Rise (DIR), Antarctica, to reconstruct discretised, vertical strain rate and velocity at millimetre resolution. The resulting profiles decay with depth, from −0.07 a−1 at the surface to ~−0.002 a−1 towards the base in strain and from −1.3 m a−1 at the surface to ~−0.5 m a−1 towards the base in velocity. Both profiles also show substantial local variability. Three coffee-can markers installed at different depths into adjacent boreholes record consistent strain rates and velocities, although averaged over longer depth ranges and subject to greater uncertainty. Measured strain-rate profiles generally compare closely with output from a 2-D ice-flow model, while the former additionally reveal substantial high-resolution variability. We conclude that repeat OPTV borehole logging represents an effective means of measuring distributed vertical strain at millimetre scale, revealing high-resolution variability along the uppermost ~100 m of DIR, Antarctica.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

Formation and evolution of an extensive blue ice moraine in central Transantarctic Mountains, Antarctica - Kassab, Christine M; Licht, Kathy J; Petersson, Rickard; Lindbäck, Katrin; Graly, Joseph A; R, Kaplan. Michael (Journal of Glaciology, 2020)
Mount Achernar moraine is a terrestrial sediment archive that preserves a record of ice-sheet dynamics and climate over multiple glacial cycles. Similar records exist in other blue ice moraines elsewhere on the continent, but an understanding of how these moraines form is limited. We propose a model to explain the formation of extensive, coherent blue ice moraine sequences based on the integration of ground-penetrating radar (GPR) data with ice velocity and surface exposure ages. GPR transects (100 and 25 MHz) both perpendicular and parallel to moraine ridges at Mount Achernar reveal an internal structure defined by alternating relatively clean ice and steeply dipping debris bands extending to depth, and where visible, to the underlying bedrock surface. Sediment is carried to the surface from depth along these debris bands, and sublimates out of the ice, accumulating over time (>300 ka). The internal pattern of dipping reflectors, combined with increasing surface exposure ages, suggest sequential exposure of the sediment where ice and debris accretes laterally to form the moraine. Subsurface structure varies across the moraine and can be linked to changes in basal entrainment conditions. We speculate that higher concentrations of debris may have been entrained in the ice during colder glacial periods or entrained more proximal to the moraine sequence.
Keywords: Antarktis; glasiologi; radar observasjoner

Rødt gull i sør - Krafft, Bjørn (Polarboken, 2020)
Keywords: Sørishavet; fiskeri; zoologi

Four principles to justify claims to jurisdiction and to natural resources in Antarctica - Mancilla, Alejandra (Yearbook of Polar Law, 2020)
Global pressure over Antarctic resources will mount in the course of the coming decades. Three factors are likely to motivate states to claim jurisdictional rights or rights to natural resources in Antarctica: climate change, dwindling natural resources in the rest of the world, and the fact that – by virtue of Article IV of the Antarctic Treaty – the question of sovereignty remains unresolved. It is high time to think about the moral dimensions that should shape Antarctic claims in the future. Is there any state or group of states more entitled than others to make such claims? What does sound management of natural resources require? How should environmental concerns factor into decisions about jurisdictional control and appropriation of natural resources? With these broad questions in the background, in this article I examine four principles of justice that figure prominently in current theories of territorial rights and rights over natural resources in political philosophy: connection, capacity, fair distribution, and need. I show how these principles have been used by states, alone or in tandem, to justify claims to jurisdiction and claims to natural resources in Antarctica. After pointing to their main strengths and weaknesses, I suggest that they may be necessary, but insufficient to build a just framework for jurisdiction and appropriation of resources in the White Continent.
Keywords: Antarktis; jus; politikk; ressurser

Life of the Antarctic ice : from deep inland to the coast - Matsuoka, Kenichi (ed.) (Norwegian Polar Institute, 2020)
Keywords: Antarktis; Dronning Maud Land; glasiologi; innlandsis; isbreer; klimaendringer; polarforskning; snø

A Mobile, Multichannel, UWB Radar for Potential Ice Core Drill Site Identification in East Antarctica: Development and First Results - Rodriguez-Morales, Fernando; Braaten, David; Trong Mai, Hoang; Paden, John; Gogineni, Prasad; Yan, Jie-Bang; Abe-Ouchi, Ayako; Fujita, Shuji; Kawamura, Kenji; Tsutaki, Shun; Liefferinge, Brice Van; Matsuoka, Kenichi; et al. (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2020)
We developed a high-performance, multichannel, ultra-wideband radar system for measurements of the base and interior of the East Antarctic Ice Sheet. We designed the radar to be of high power (4000-W peak) yet portable and to be able to operate with 60-MHz bandwidth at a center frequency of 200 MHz, providing high sensitivity and fine vertical resolution relative to current technology. We used the radar to perform extensive measurements as a part of a multinational collaboration. We collected data onboard a tracked vehicle outfitted with an array of high-gain antennas. We sounded 2- to 3-km thick ice near Dome Fuji. Preliminary ice thickness data match those obtained via semicoincident measurements performed with a different surface-based pulse modulated radar system operated during the same field campaign, as well as previous airborne measurements. In addition, we mapped internal reflection horizons with fine vertical resolution from 300 m below the ice surface to ∼100 m above the bed. In this article, we provide a detailed overview of the radar instrument design, implementation, and field measurement setup. We present sample data to illustrate its capabilities and discuss how the data collected with it will be valuable for the assessment of promising drilling sites to recover ice cores that are 0.9–1.5 million years old.
Keywords: Antarktis; glasiologi; innlandsis; iskjerner

Antarctic Futures: An Assessment of Climate-Driven Changes in Ecosystem Structure, Function, and Service Provisioning in the Southern Ocean - Rogers, Alex David; Frinault, Betina A V; Barnes, D K A; Bindoff, Nathaniel Lee; Downie, Rod; Ducklow, Hugh W; Friedlaender, A S; Hart, T; Hill, Simeon; Hofmann, E E; Linse, Katrin; McMahon, Clive R; et al. (Annual Review of Marine Science, 2020)
In this article, we analyze the impacts of climate change on Antarctic marine ecosystems. Observations demonstrate large-scale changes in the physical variables and circulation of the Southern Ocean driven by warming, stratospheric ozone depletion, and a positive Southern Annular Mode. Alterations in the physical environment are driving change through all levels of Antarctic marine food webs, which differ regionally. The distributions of key species, such as Antarctic krill, are also changing. Differential responses among predators reflect differences in species ecology. The impacts of climate change on Antarctic biodiversity will likely vary for different communities and depend on species range. Coastal communities and those of sub-Antarctic islands, especially range-restricted endemic communities, will likely suffer the greatest negative consequences of climate change. Simultaneously, ecosystem services in the Southern Ocean will likely increase. Such decoupling of ecosystem services and endemic species will require consideration in the management of human activities such as fishing in Antarctic marine ecosystems.
Keywords: Sørishavet; biodiversitet; klimaendringer; marine økosystemer; miljøpåvirkning

Glacial erosion estimates for the Dronning Maud Land Mountains, based on low-temperature thermochronology - Sirevaag, Hallgeir; Ksienzyk, Anna Katharina; Jacobs, Joachim (Norsk Geologisk Forening, 2020)
Keywords: Dronning Maud Land; geologi; termokronologi

På tokt i Dronning Maud Land - Steen, Harald ("Kronprins Haakon", 2020)
Keywords: Sørishavet; ekspedisjoner; marinbiologi

Polar Regions in the Anthropocene - Summerhayes, Colin; Zalasiewicz, Jan; Vidas, Davor; Williams, Mark (Research handbook on polar law, 2020)
Keywords: Antarktis; geologi; havrett; internasjonal; polarområdene

Regulating the Natural Resources in the Antarctic Region: A Historical Review - Basberg, Bjørn L (The political economy of resource regulation : an international and comparative history, 1850-2015, 2019)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalindustri; naturressurser; pelagisk; økonomi

Den siste olje - Berge, Aslak (Octavian forlag AS, 2019)
Over seks tiår fylte glinsende fett fra hundretusenvis av hval råstoffbehov til multinasjonale konserners margarin- og såpeprodukter. Hoffleverandørene var norske hvalfangere. Fra spekkjelene like etter århundreskiftet ble fyrt opp på Sør-Georgia til det flytende kokeriet Kosmos IV ankret opp i Sandefjord på slutten av 1960-tallet, skulle hvalfangst dominere og forme utviklingen av finansmarked, konsumvarer og kapitalisme i Norge. Dette er en fortelling om eksplosivt voksende rikdom og merkevarebygging, men også en biologisk tragedie. Et nådeløst møte mellom jordens største dyr, effektiv fangsteknologi og konsumindustri. Dette er en flerfasettert historie om et kapitalfattig lands industrialisering, skattesky redere og multinasjonale fettkjemper, men også om ubegrensede offer og tap. Om norsk polarimperialisme og globalt salg utfordret av stormakter og skiftende konjunkturer. Dette er historien om "Den siste olje".
Keywords: Norge; Sørishavet; historie; hvalfangstindustri; hvalindustri; pelagisk; økonomi

A continent of and for whiteness?: “White” colonialism and the 1959 Antarctic Treaty - Mancilla, Alejandra (Polar Record, 2019)
There are at least four ways in which Antarctic colonialism was white: it was paradigmatically performed by white men; it consisted in the taking of vast, white expanses of land; it was carried out with a carte blanche (literally, “blank card”) attitude; and it was presented to the world as a white, innocent adventure. While the first, racial whiteness has been amply problematised, I suggest that the last three illuminate yet other moral wrongs of the Antarctic colonial project. Moreover, they might be constitutive of a larger class of “white” colonialisms beyond the White Continent.
Keywords: Antarktis; historie; politikk; samfunnsfag

Roald Amundsen’s sled dogs : the sledge dogs who helped discover the South Pole - Tahan, Mary R (Springer, 2019)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; sledehunder; trekkhunder

Proterozoic evolution of central Dronning Maud Land (East Antarctica) from Rodinia to Gondwana - Wang, Cheng-Cheng; Jacobs, Joachim; Elburg, Marlina; Läufer, Andreas ([ISAES], 2019)
Keywords: Dronning Maud Land; geologi

Polarårboken Glacier (Polarboken, 2018)
Keywords: Antarktis; geografi; glasiologi

I Roald Amundsens fotspor til Sydpolen med besøk på Bettytoppen - Furholt, Astrid (Polarboken, 2018)
Keywords: Antarktis; ekspedisjoner; historie

Ice-rise stratigraphy reveals changes in surface mass balance over the last millennia in Dronning Maud Land - Goel, Vikram; Martín, Carlos; Matsuoka, Kenichi (Journal of Glaciology, 2018)
We use ice flow modelling to simulate the englacial stratigraphy of Blåskimen Island, an ice rise in Dronning Maud Land and elucidate the evolution of this data-sparse region. We apply a thermo-mechanically coupled Elmer/Ice model to a profile along flowlines and through the ice-rise summit, where surface mass balance (SMB), flow velocity and ice stratigraphy were recently measured. We conclude that: (i) the ice rise is presently thickening at a rate of 0.5~0.6 m ice equivalent per year (mieq a−1), which is twice an earlier estimate using the field data and the input–output method; (ii) present thickening started 20–40 years in the past, before which the ice rise was in a steady state; (iii) SMB contrast between the upwind and downwind slopes was stronger than the present value by ~23% (or 0.15 mieq a−1) prior to ~1100 years ago. Since then, this contrast has been decreasing overall. We surmise that these SMB changes are likely a result of synoptic-scale atmospheric changes, rather than local atmospheric changes controlled by local ice topography. Our technique effectively assimilates geophysical data, avoiding the complexity of ice flow beneath the ice divide. Thus, it could be applied to other ice rises to elucidate the recent glacial retreat.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

Antarctic environmental protection: strengthening the links between science and governance - Hughes, Kevin A; Constable, Andrew; Frenot, Yves; López-Martinez, Jerónimo; McIvor, Ewan; Njåstad, Birgit; Terauds, Aleks; Liggett, Daniela; Roldan, Gabriela; Wilmotte, Annick; Xavier, José C (Environmental Science & Policy, 2018)
The Antarctic has significant environmental, scientific, historic, and intrinsic values, all of which are worth protecting into the future. Nevertheless, the area is subject to an increasing level and diversity of human activities that may impact these values within marine, terrestrial and cryosphere environments. Threats to the Antarctic environment, and to the aforementioned values, include climate change, pollution, habitat destruction, wildlife disturbance and non-native species introductions. Over time, a suite of legally binding international agreements, which form part of the Antarctic Treaty System (ATS), has been established to help safeguard the Antarctic environment and provide a framework for addressing the challenges arising from these threats. Foremost among these agreements are the Protocol on Environmental Protection to the Antarctic Treaty and the Convention on the Conservation of Antarctic Marine Living Resources. Many scientists working in Antarctica undertake research that is relevant to Antarctic environmental policy development. More effective two-way interaction between scientists and those responsible for policy development would further strengthen the governance framework, including by (a) better communication of policy makers’ priorities and identification of related science requirements and (b) better provision by scientists of ‘policy-ready’ information on existing priorities, emerging issues and scientific/technological advances relevant to environmental protection. The Scientific Committee on Antarctic Research (SCAR) has a long and successful record of summarizing policy-relevant scientific knowledge to policy makers, such as through its Group of Specialists on Environmental Affairs and Conservation (GOSEAC) up to 2002, currently the SCAR Standing Committee on the Antarctic Treaty System (SCATS) and recently through its involvement in the Antarctic Environments Portal. Improvements to science-policy communication mechanisms, combined with purposeful consideration of funding opportunities for policy-relevant science, would greatly enhance international policy development and protection of the Antarctic environment.
Keywords: Antarktis; miljøvern

The relationship between coastal weather and foraging behaviour of chinstrap penguins, Pygoscelis antarctica - Lowther, Andrew D; Trathan, Phil; Tarroux, Arnaud; Lydersen, Christian; Kovacs, Kit M (ICES Journal of Marine Science, 2018)
There is increasing interest in using higher-trophic level predators as ecosystem indicators because their performance is presumed to be linked to the overall function of the ecosystem that supports them. In the southwest Atlantic sector of the Southern Ocean, Antarctic krill (Euphausia superba) supports huge predator populations as well as a growing commercial fishery. To utilize information from the ecosystem in an adaptive framework for sustainably managing krill catch levels, performance indices of krill predators have been proposed as a proxy for krill abundance. However, there are several potentially confounding sources of variability that might impact predator performance such as the effects of environmental variability and fishing pressure on krill availability at scales relevant to predators. In this context, our study capitalises on the occurrence of an unexpected El Niño event to characterise how environmental variability can drive changes in predator foraging behaviour. We demonstrate a clear link between coastal downwelling and changes in the at-sea habitat usage of chinstrap penguins (Pygoscelis antarctica) foraging in a local krill fishing area. Penguins tracked from their breeding colonies on Powell Island, Antarctic Peninsula, undertook fewer, longer foraging trips during the downwelling-affected season compared with the season where no such downwelling was detected, suggesting that changes in climate-driven oceanography may have reduced krill availability along the northern shelf of the island. Our study demonstrates that penguin foraging behaviour is modified by scale-dependent processes, which if not accounted for may result in erroneous conclusions being drawn when using penguins as bioindicators of krill abundance.
Keywords: Sørishavet; marinbiologi; meteorologi; ornitologi; pingviner; økologi

The moral limits of territorial claims in Antarctica - Mancilla, Alejandra (Ethics & International Affairs, 2018)
By virtue of the Antarctic Treaty, signed in 1959, the territorial claims to Antarctica of seven of the original signatories were held in abeyance or “frozen.” Considered by many as an exemplar of international law, the Antarctic Treaty System has come to be increasingly questioned, however, in a very much changed global scenario that presents new challenges to the governance of the White Continent. In this context, it is necessary to gain a clearer understanding of the moral weight of those initial claims, which stand (despite being frozen) as a cornerstone of the treaty. The aim of this article is to offer an appraisal of such claims, which may be divided into two main kinds: those grounded on some relevant link to the territory, and those grounded on official documents and geographical doctrines. After pointing to the limitations and challenges that they face, I conclude with some remarks about how this assessment ought to serve as a starting point to rethink the territorial status of Antarctica.
Keywords: Antarktis; historie; jus; politikk; ressurser

Kapten Roald Amundsen: I vargskinnspäls och textil. Blir först på Sydpolen - Norén, Karl-Gunnar (Polarfararnas kläder : på liv och död, 2018)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; polarekspedisjoner; utstyr

Ground displacements on Bouvet Island using SAR Interferometry (18/2018) - Rouyet, Line; Lauknes, Tom Rune; Larsen, Yngvar; Norut (2018)
Based on 8 RADARSAT-2 Ultrafine scenes from December 2017 to June 2018, ground displacements close to the Norvegia research station of Bouvet Island have been measured using Synthetic Aperture Radar Interferometry (InSAR). The results show that loss of coherence related to erosion processes is affecting the coast west from the station. The mean velocity maps identify a well-defined unstable area south from Norvegia and by applying the Small Baseline Subset (SBAS) time-series InSAR method, we are able to provide time series during the considered time period. The results tend to indicate that the area north from the current location of Norvegia station is more stable.
Keywords: Bouvetøya; geovitenskap; interferometri

Psychological Hibernation in Antarctica - Sandal, Gro Mjeldheim; van deVijver, Fons J. R.; Smith, Nathan (Frontiers in Psychology, 2018)
Human activity in Antarctica has increased sharply in recent years. In particular during the winter months, people are exposed to long periods of isolation and confinement and an extreme physical environment that poses risks to health, well-being and performance. The present study aimed to gain a better understanding of processes contributing to psychological resilience in this context. Specifically, the study examined how the use of coping strategies changed over time, and the extent to which changes coincided with alterations in mood and sleep. Two crews (N = 27) spending approximately 10 months at the Concordia station completed the Utrecht Coping List, the Positive and Negative Affect Schedule (PANAS), and a structured sleep diary at regular intervals (x 9). The results showed that several variables reached a minimum value during the midwinter period, which corresponded to the third quarter of the expedition. The effect was particularly noticeable for coping strategies (i.e., active problem solving, palliative reactions, avoidance, and comforting cognitions). The pattern of results could indicate that participants during Antarctic over-wintering enter a state of psychological hibernation as a stress coping mechanism.
Keywords: Antarktis; overvintring; polarekspedisjoner; polarforskere; polarområdene; psykologi

Hvaleventyret : hvordan vi nesten utryddet det største dyret som har levd - Tjernshaugen, Andreas (Kagge, 2018)
Historien om jakten på blåhvalen, verdens største dyr. Blåhvalen var nær ved å bli utryddet av den moderne hvalfangsten med raske båter, sprenggranater og harpunkanon. Lenge utgjorde Vestfold verdens hvalfangstsentrum, og på det meste forlot ti tusen norske menn familien og dro på hvalfangst i fremmede farvann. Det var et blodslit, og et eventyr. Helt fra starten kom det advarsler om at hvalene kunne bli utryddet. For blåhvalen var det på nære nippet. Underarten i Antarktis, som blir aller størst, regnes fortsatt som kritisk truet. I sluttspillet om blåhvalens skjebne ble Norge utfordret av både Storbritannia og Nazi-Tyskland, Japan og Sovjetunionen, som kastet seg inn i kampen om Sørishavets rikdommer. "Hvaleventyret" er en medrivende historie om blåhvalen og hvalfangsten. Den forteller om hvalenes årlige trekk mellom isen og varmere hav, om hvalfangernes livsfarlige pionerferder i polhavene, og om kampen for å redde de siste blåhvalene.
Keywords: Nordmenn; Norge; Sørishavet; dyrevern; hvaler; hvalfangst; hvalindustri; pelagisk; sjøpattedyr

Versatility of GC-Orbitrap mass spectrometry for the ultra-trace detection of persistent organic pollutants in penguin blood from Antarctica - Warner, Nicholas; Cojocariu, Cristian; Scientific, ThermoFisher (2018)
Using GC Orbitrap mass spectrometry to address analytical challenges with trace level detection of persistent organic pollutants in Antarctica.
Keywords: Antarktis; biologi; miljøgifter; pingviner; zoologi

A new compiled geological map of Dronning Maud Land, Antarctica - Abu-Alam, Tamer; Elvevold, Synnøve; Jacobs, Joachim; Myhre, Per Inge (Norsk Geologisk Forening (NGF), 2017)
Dronning Maud Land in East Antarctica represents the central part of the Gondwana supercontinent. Geological mapping and investigation of Dronning Maud Land have been carried out over the last 40-50 years. The existing geological maps of Dronning Maud Land are, for a large part, based on fairly old data, which makes these maps inhomogeneous. The maps are at different scales, contain different levels of details, and the standards for classification of the rock units may also differ between the maps. This limits the ability to use these map to draw an overview tectonic model of the evolution of Dronning Maud Land. Moreover, the existing topographic dataset from Dronning Maud Land is based on fairly old topographic maps (1960s), and there is a discrepancy between the topographic dataset and the more recent Landsat images. There are still unmapped areas.
Keywords: Dronning Maud Land; geologi

Sett fra luften - Berg, Thomas Reinertsen (Verdensteater : kartenes historie, 2017)
Keywords: ekspedisjoner; flyfotografering; karthistorie; kartlegging; kartografi

Exploring the Recovery Lakes region and interior Dronning Maud Land, East Antarctica, with airborne gravity, magnetic and radar measurements - Forsberg, Rene; Olesen, Arne; Jordan, Tom; Matsuoka, Kenny; Zakrajsek, Andres; Ghidella, Marta; Greenbaum, Jamin (Geological Society, London, Special Publications, 2017)
Long-range airborne geophysical measurements were carried out in the ICEGRAV campaigns, covering hitherto unexplored parts of interior East Antarctica and part of the Antarctic Peninsula. The airborne surveys provided a regional coverage of gravity, magnetic and icepenetrating radar measurements for major Dronning Maud Land ice stream systems, from the grounding lines up to the Recovery Lakes drainage basin, and filled in major data voids in Antarctic data compilations, such as AntGP for gravity data, ADMAP for magnetic data and BEDMAP2 for ice thickness data and the sub-ice topography. We present the first maps of gravity, magnetic and ice thickness data and bedrock topography for the region and show examples of bedrock topography and basal reflectivity patterns. The 2013 Recovery Lakes campaign was carried out with a British Antarctic Survey Twin Otter aircraft operating from the Halley and Belgrano II stations, as well as a remote field camp located at the Recovery subglacial Lake B site. Gravity measurements were the primary driver for the survey, with two airborne gravimeters (Lacoste and Romberg and Chekan-AM) providing measurements at an accuracy level of around 2 mGal r.m.s., supplementing GOCE (Gravity Field and Steady-State Ocean Circulation Explorer) satellite data and confirming an excellent sub-milligal agreement between satellite and airborne data at longer wavelengths.
Keywords: Dronning Maud Land; geofysikk; glasiologi

Glaciological settings and recent mass balance of Blåskimen Island in Dronning Maud Land, Antarctica - Goel, Vikram; Brown, Joel; Matsuoka, Kenichi (The Cryosphere, 2017)
The ice-shelf-fringed coast of Dronning Maud Land in East Antarctica contains numerous ice rises that influence the dynamics and mass balance of the region. However, only a few of these ice rises have been investigated in detail. Here, we present field measurements of Blåskimen Island, an isle-type ice rise adjacent to Fimbul Ice Shelf. This ice rise is largely dome shaped, with a pronounced ridge extending to the south-west from its summit (410 m a.s.l.). Its bed is mostly flat and about 100 m below the current sea level. Shallow radar-detected isochrones dated with a firn core reveal that the surface mass balance is higher on the south-eastern (upwind) slope than on the north-western (downwind) slope by ∼ 37 %, and this pattern has persisted for at least the past decade. Moreover, arches in radar stratigraphy suggest that the summit of the ice rise has been stable for ∼ 600 years. Ensemble estimates of the mass balance using the input–output method show that this ice rise has thickened by 0.12–0.37 m ice equivalent per year over the past decade.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

Carsten Borchgrevink and the Southern Cross Expedition, 1898-1900 - Riffenburgh, Beau; Kløver, Geir O (Red.) (The Fram Museum, 2017)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Norway and the Antarctic - Stephenson, Robert B; [Barr, Susan] (The Erebus and Terror Press, 2017)
Keywords: Antarktis; Nordmenn; norske ekspedisjoner; polarfarere

At-Sea Distribution and Prey Selection of Antarctic Petrels and Commercial Krill Fisheries - Descamps, Sébastien; Tarroux, Arnaud; Cherel, Yves; Delord, Karine; Godø, Olaf Rune; Akiko, Kato; Krafft, Bjørn A; Lorentsen, Svein-Håkon; Ropert-Coudert, Yan; Skaret, Georg; Varpe, Øystein (PloS One, 2016)
Kommersielle fiskerier kan påvirke marine økosystemer og bestander av topp-predatorer som sjøfugl. I Sørishavet foregår et ekstensivt fiske etter Antarktisk krill (Euphausia superba), og dette er antatt å øke. En sammenligning av fordeling og uttak hos fiskeriene og tilsvarende hos topp-predatorene er nødvendig for å forutsi fiskerirelaterte påvirkninger på krillavhengige predatorer. I dette studiet kartla vi næringssøksområdene hos Antarktispetrell (Thalassoica antarctica) som hekker i verdens største koloni (Svarthammaren, Dronning Maud land) over en treårsperiode. Vi fant at det romlige overlappet mellom krillfiskerier og næringssøkende Antarktispetrell generelt var lite. Konkurranse mellom Antarktispetrell og krill-fiskerier er for tiden neglisjerbart, men kan øke hvis fiskeriet etter krill øker.
Keywords: Dronning Maud Land; Sørishavet; fiskeriforvaltning; krill; marinbiologi; ornitologi; økosystem

Den norsk-brittisk-svenska Antarktisexpeditionen (NSBX) - Holmlund, Per; Martinsson, Tyrone (Frusna ögonblick : svensk polarfotografi 1861-1980, 2016)
Keywords: Antarktis; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fotografi; fotohistorie; polarekspedisjoner

Delivering 21st century Antarctic and Southern Ocean science - Kennicutt, Mahlon C I I; Kim, Yeadong; Rogan-Finnemore, Michelle; Anandakrishnan, Sridhar; Chown, Steven L; Colwell, Steven (Antarctic Science, 2016)
The Antarctic Roadmap Challenges (ARC) project identified critical requirements to deliver high priority Antarctic research in the 21st century. The ARC project addressed the challenges of enabling technologies, facilitating access, providing logistics and infrastructure, and capitalizing on international co-operation. Technological requirements include: i) innovative automated in situ observing systems, sensors and interoperable platforms (including power demands), ii) realistic and holistic numerical models, iii) enhanced remote sensing and sensors, iv) expanded sample collection and retrieval technologies, and v) greater cyber-infrastructure to process ‘big data’ collection, transmission and analyses while promoting data accessibility. These technologies must be widely available, performance and reliability must be improved and technologies used elsewhere must be applied to the Antarctic. Considerable Antarctic research is field-based, making access to vital geographical targets essential. Future research will require continent- and ocean-wide environmentally responsible access to coastal and interior Antarctica and the Southern Ocean. Year-round access is indispensable. The cost of future Antarctic science is great but there are opportunities for all to participate commensurate with national resources, expertise and interests. The scope of future Antarctic research will necessitate enhanced and inventive interdisciplinary and international collaborations. The full promise of Antarctic science will only be realized if nations act together.
Keywords: Antarktis; forskning; vitenskap

Jason-ekspedisjonene 1892-1894, Antarctic-ekspedisjonen 1901-1904 - Larsen, Carl Anton; Kløver, Geir O (Red.) (Frammuseet, 2016)
Keywords: Antarctic ekspedisjonen; Antarktis; Carl Anton Larsen; D/S Antarctic; D/S Jason; Jason ekspedisjonene; Sørishavet; dagbok; ekspedisjoner; hvalfangere; hvalfangst; polarområdene

Gåten om Roald Amundsens varde på Bettyfjellet i Antarktis - Mehlum, Fridtjof (Polarboken, 2016)
Keywords: Antarktis; ekspedisjoner; historie

Polheim: teltet på Sydpolen - Melgård, Anne (Polarboken, 2016)
Keywords: Antarktis; ekspedisjoner; historie

Chinstrap and macaroni penguin diet and demography at Nyrøysa, Bouvetøya - Niemandt, Corne; Kovacs, Kit M; Lydersen, Christian; Dyer, Bruce M; Isaksen, Kjell; Hofmeyr, G J Greg; Mehlum, Fridtjof; de Bruyn, P J Nico (Antarctic Science, 2016)
Keywords: Bouvetøya; klimaendringer; krill; pelsseler; pingviner; plankton

"Big Science" for meteorologene - Nilsen, Yngve; Vollset, Magnus (Vinden dreier : meteorologiens historie i Norge, 2016)
Keywords: Bouvetøya; ekspedisjoner; forskning; meteorologi

Ice core evidence for a 20th century increase in surface mass balance in coastal Dronning Maud Land, East Antarctica - Philippe, Morgane; Tison, Jean-Louis; Fjøsne, Karen; Hubbard, Bryn; Kjær, Helle A; Lenaerts, Jan T M; Drews, Reinhard; Sheldon, Simon G; De Bondt, Kevin; Claeys, Philippe; Pattyn, Frank (The Cryosphere, 2016)
Ice cores provide temporal records of surface mass balance (SMB). Coastal areas of Antarctica have relatively high and variable SMB, but are under-represented in records spanning more than 100 years. Here we present SMB reconstruction from a 120 m-long ice core drilled in 2012 on the Derwael Ice Rise, coastal Dronning Maud Land, East Antarctica. Water stable isotope (δ18O and δD) stratigraphy is supplemented by discontinuous major ion profiles and continuous electrical conductivity measurements. The base of the ice core is dated to AD 1759 ± 16, providing a climate proxy for the past  ∼ 250 years. The core's annual layer thickness history is combined with its gravimetric density profile to reconstruct the site's SMB history, corrected for the influence of ice deformation. The mean SMB for the core's entire history is 0.47 ± 0.02 m water equivalent (w.e.) a−1. The time series of reconstructed annual SMB shows high variability, but a general increase beginning in the 20th century. This increase is particularly marked during the last 50 years (1962–2011), which yields mean SMB of 0.61 ± 0.01 m w.e. a−1. This trend is compared with other reported SMB data in Antarctica, generally showing a high spatial variability. Output of the fully coupled Community Earth System Model (CESM) suggests that, although atmospheric circulation is the main factor influencing SMB, variability in sea surface temperatures and sea ice cover in the precipitation source region also explain part of the variability in SMB. Local snow redistribution can also influence interannual variability but is unlikely to influence long-term trends significantly. This is the first record from a coastal ice core in East Antarctica to show an increase in SMB beginning in the early 20th century and particularly marked during the last 50 years.
Keywords: Dronning Maud Land; glasiologi; iskjerner

C.A. Larsen : explorer, whaler & family man - Riffenburgh, Beau (Red.); Kløver, Geir O (Red.) (The Fram Museum, 2016)
Keywords: Antarctic ekspedisjonen; Antarktis; Carl Anton Larsen; D/S Antarctic; D/S Jason; Jason ekspedisjonene; Weddellhavet; hvalfangere; hvalfangst; oppdagelsesreiser; polarforskning

Animals as instruments of Norwegian imperial authority in the interwar Arctic - Roberts, Peder; Jørgensen, Dolly (Journal for the History of Environment and Society, 2016)
During the first half of the twentieth century a number of individuals in Norway participated in the transfer of animals from both the Arctic to the Antarctic regions and vice versa. These projects may be conceptualized as a form of imperial acclimatization, following in the footsteps of earlier attempts to transplant both plants and animals from their indigenous ranges to new geographic locations for both practical and recreational purposes. Reindeer were introduced to the island of South Georgia before World War I as Norwegian whalers turned a space previously uninhabited by humans into the operational hub of a booming Antarctic whaling industry. The successful transplantation of reindeer was followed by less successful attempts to transfer muskoxen from Greenland to Svalbard and the Scandinavian mainland, penguins from the Antarctic to the coast of Norway, and dreams of transferring fur seals from south to north. We argue that these attempts constituted both practical attempts to “enrich” the fauna of discrete habitats, but also expressions of Norwegian authority over the polar regions at a time when imperial ambitions in both the Arctic and Antarctic had significant traction within Norway. The transplanted animals may thus be conceived as geopolitical instruments – mastery over fauna as being a means of expressing mastery over space.
Keywords: Antarktis; Bouvetøya; Norge; geopolitikk; hvalfangst; polarområdene

The canine explorers – the sled dogs who helped Roald Amundsen reach the South Pole - Tahan, Mary R (Journal of Antarctic Affairs, 2016)
One hundred Greenland dogs were purchased by Roald Amundsen from the Royal Greenland Trading Company in September 1909 ostensibly for a North Pole expedition, but secretly to use to reach the South Pole. Amundsen considered the dogs “equipment”. He was a complicated character in a very different time. And he compulsively pursued his mission. His actions perhaps are seen differently from the 21st century perspective and in light of our evolving attitude toward animals, especially dogs. This paper presents the facts of what happened concerning the sled dogs, using Amundsen’s own statements in his books, diaries, and letters, as well as the expedition members’ journal entries and personal letters. It focuses on the dogs who made Amundsen’s exploration possible, and who helped humankind discover the final undiscovered part of our world. Amundsen began his Norwegian expedition with 97 sturdy canine souls, who were taken on board the Fram near the coast of Kristiansand in August 1910. Through births and deaths on the ship during their five-month journey south, the dogs’ number swelled to 116 upon arrival in Antarctica. Adults and puppies alike withstood the roller-coaster ride of the Fram on the ocean waters, the heat of the tropics near the equator, and the freezing winter of Antarctica. Taking into account the birth of puppies on the ship and at their Antarctic home Framheim, the actual number of dogs involved in this significant moment in history doubles to over two hundred. But, after initially nurturing and protecting the dogs, Amundsen proceeded to cull them throughout the expedition, slaughtering those he deemed unnecessary or weak, and destroying those who had served their purpose. Amundsen began his South Pole trek in October 1911 with 52 brave canines, and returned with 11, as a result of unnatural, forced attrition. The dogs were nearly starved; at times when they were fed, it was the flesh of their fallen comrades they were given to line their empty stomachs. And yet the dogs all performed their roles brilliantly, even when death was their reward. The sled dogs were the heart and power of the South Pole expedition. The intent of this article is to shine a light on the dogs’ population, accomplishments, and sacrifices, and to give them their due recognition and place in history.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; sledehunder; trekkhunder

Frozen voices: Women, silence and Antarctica - Blackadder, Jesse (Antarctica : music, sounds and cultural connections, 2015)
This chapter explores a different kind of Antarctic silence: the silencing of certain stories and voices. It’s the silence of the earliest female travellers to Antarctica.The voices of the earliest female travellers are silent and their stories remain untold, partly because there’s no place for them in the dominant Antarctic narrative of exploration and conquest. Reimagining them through fiction is one way — though with potential pitfalls — to ‘unfreeze’ those stories.
Keywords: Antarktis; Nordmenn; ekspedisjoner; kvinner; oppdagelsesreiser

The WEGAS / GEA IV Geophysical Survey in eastern and southern Dronning Maud Land - Eagles, Graeme; Ruppel, Antonia; Steinhage, Daniel; Jokat, Wilfried; Läufer, Andreas; Jacobs, Joachim ([German Society for Polar Research], 2015)
The Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research (AWI) and the Federal Institute for Geosciences and Natural Resources (BGR) collected around 150 hours of new gravity, magnetic and ice-penetrating radar data from east and south of Princess Elisabeth station in Dronning Maud Land between 2013 and 2015. Survey lines were spaced 10 km apart. The 2013/2014 and 2014/2015 used different gravimeters; a LaCoste and Romberg AirSea gravimeter (LCR) at constant barometric altitude and a Gravimetric Technologies GT2A gravimeter at constant ground separation. Both surveys used a Scintrex Cs-3 caesium vapour magnetometer mounted in a tail boom with compensation for the airframe calculated using a fuselage-mounted three-component fluxgate magnetometer. The GT2A gravity data reflect the effects of short-wavelength density contrasts between basement rocks and the ice sheet more reliably than the LCR data. Cross-over analysis suggests the repeatability of data collection with the GT2A lies at the sub-milliGal level. A broad subglacial channel that separates eastern Sør Rondane from the Yamato Belgica Mountains is evident in the gravity data. In the south of the survey region, the data reveal a dendritic pattern of subglacial valleys that converge towards the SW. Strong NS-trending magnetic anomalies coincide with the Yamato-Belgica Mountains. Further west, subtler ESE-trending anomalies confirm proposals that the SE Dronning Maud Land province continues into the region south of eastern Sør Rondane. An unexpected feature of both data sets is the apparent termination of the anomaly patterns associated with the province at a NNW-trending anomaly running south of Princess Elisabeth.
Keywords: Dronning Maud Land; geofysikk; geovitenskap

East Antarctica and supercontinent configuration: the Dronning Maud Land perspective - Jacobs, Joachim; Elburg, Marlina; Läufer, Andreas; Jokat, Wilfried (Japan Geoscience Union, 2015)
The geology of East Antarctica and its correlation in major supercontinents is highly speculative, since only a very small part of it is exposed. Therefore a better connection between geology and geophysics is needed in order to correlate exposed regions with ice-covered, geophysically-defined, blocks. In Dronning Maud Land (DML), two distinct late Mesoproterozoic/early Neoproterozoic tectono-metamorphic provinces appear, separated by the major, NE-trending Forster Magnetic Anomaly and South Orvin Shear Zone. To the west of this lineament, the Maud Belt has clear affinities with Grenville-age continent-continent mobile belts. East of the Forster Magnetic Anomaly, juvenile rocks with early Neoproterozoic age (Rayner-age) and an accretionary character crop out. The international GEA-II expedition (2012) targeted a white spot on the geological map immediately to the E of the Forster Magnetic Anomaly. This area allows the characterization and ground-truthing of a large and mostly ice-covered region, the SE DML Province that had previously been interpreted as an older cratonic block. However, new SHRIMP/SIMS zircon analyses and their geochemistry indicates that the exposed basement consists of a ca. 1000-900 Ma juvenile terrane that is very similar to rocks in Sor Rondane. It lacks significant metamorphic overprint at the end of crust formation, but it shows medium to high-grade overprinting between ca. 630-520 Ma, associated with significant felsic melt production, including A-type granitoid magmatism. Therefore, the aeromagnetically distinct SE DML province does neither represent the foreland of a Late Neoproterozoic/EarlyPaleozoic mobile belt, nor a craton, as has previously been speculated. It more likely represents the more juvenile, westward continuation of Rayner-age crust (1000-900 Ma). To the west it abuts along the NE-trending Forster Magnetic Anomaly. The latter is interpreted as a suture, which separates typical Grenville-age crust of the Maud Belt (ca. 1200-1030 Ma) to the W from Rayner-age crust to the E. Therefore the larger eastern part of DML has clearly Indian affinities. Its juvenile character with a lack of metamorphic overprint at the end of crust formation points to an accretionary history along this part of the Indian segment of Rodinia, immediately following final Rodinia assembly.
Keywords: Dronning Maud Land; geofysikk; geologi

Modern foraminifera assemblages in the Amundsen Sea Embayment - Jernas, Patrycja Ewa; Kuhn, Gerhard; Hillenbrand, Claus-Dieter; Forwick, Matthias; Rasmussen, Tine Lander; Mackensen, Andreas; Schröder, Michael; Smith, James; Klages, Johann Philipp; Szczucinski, W (Norsk Geologisk Forening (NGF), 2015)
The West Antarctic Ice Sheet (WAIS) is considered the most unstable part of the Antarctic Ice Sheet. As the WAIS is mostly grounded below sea level, its stability is of great concern. A collapse of large parts of the WAIS would result in a significant global sea-level rise. At present, the WAIS shows dramatic ice loss in its Amundsen Sea sector, especially in Pine Island Bay. Pine Island Glacier (PIG) is characterised by fast flow, major thinning and rapid grounding-line retreat. Its mass los over recent decades is generally attributed to melting caused by the inflow of warm Circumpolar Deep Water (CDW). Future melting of PIG may result in a sea level tipping point, because it could trigger widespread collapse of the WAIS, especially when considering ongoing climate change.
Keywords: Sørishavet; geologi; innlandsis; klimaendringer

Modern foraminifera assemblages in the Amundsen Sea Embayment - Jernas, Patrycja Ewa; Kuhn, Gerhard; Hillenbrand, Claus-Dieter; Rasmussen, Tine Lander; Forwick, Matthias; Mackensen, Andreas; Schröder, Michael; Smith, James; Klages, Johann Philipp (2015)
The West Antarctic Ice Sheet (WAIS) is considered the most unstable part of the Antarctic Ice Sheet. As the WAIS is mostly grounded below sea level, its stability is of great concern. A collapse of large parts of the WAIS would result in a significant global sea-level rise. At present, the WAIS shows dramatic ice loss in its Amundsen Sea sector, especially in Pine Island Bay. Pine Island Glacier (PIG) is characterised by fast flow, major thinning and rapid grounding-line retreat. Its mass los over recent decades is generally attributed to melting caused by the inflow of warm Circumpolar Deep Water (CDW). Future melting of PIG may result in a sea level tipping point, because it could trigger widespread collapse of the WAIS, especially when considering ongoing climate change.
Keywords: Sørishavet; geologi; innlandsis; klimaendringer

The great white silence : den offisielle filmen om Robert Falcon Scotts sydpolekspedisjon og en vurdering av ekspedisjonen - Lund, Vidar (Maritimt Magasin Historie, 2015)
Keywords: Antarktis; Robert Falcon Scott; Sydpolsekspedisjonen; oppdagelsesreiser

Belåtna svenskar i Antarktis - Lundin, Kjell (Pemmikan : en hårdkokt historia, 2015)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ernæring; mat

"Toffe karer spiser pemmikan" - Lundin, Kjell (Pemmikan : en hårdkokt historia, 2015)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ernæring; mat

Leadership lessons from the race to the South Pole : why Amundsen lived and Scott died - O'Connell, Fergus (Praeger, 2015)
A project management expert identifies methods for running any project successfully based on lessons learned from the exploits of two storied explorers.
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; oppdagelsesreiser

Seismic signals from large, tabular icebergs drifting along the Dronning Maud Land coast, Antarctica, and their significance for iceberg monitoring - Pirli, Myrto; Matsuoka, Kenichi; Schweitzer, Johannes; Moholdt, Geir (Journal of Glaciology, 2015)
In this study, we analyze a large dataset of seismic signals, recorded by station TROLL in Dronning Maud Land, Antarctica. The signals, recorded in April–December 2012, came from sources near the edge of the ice shelves, at distances of 230–500 km from TROLL. The sources, which moved westward with time, could be associated with four large, tabular icebergs, drifting between 15° E and 8° W. Combining the seismological data with information from satellite remote sensing, we find that one-third of the signals can be attributed to individual icebergs. The trajectories of three of the associated icebergs are known through iceberg-tracking databases, whereas the fourth, a fragment of one of the other three, is untracked, and only scarce information is available from satellite imagery. The observed seismic signals exhibit a wide variety of frequency characteristics, from unstructured episodes to occurrences of iceberg harmonic tremor. Although we are not able to determine the exact cause of the signals, we classify them into five classes on a phenomenological basis. This study demonstrates the potential of regional seismic networks for iceberg monitoring as supplementary resources to information obtained with remote-sensing technologies.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; havis; isfjell; teknologi

Lateral extrusion at the Eastern margin of the East African-Antarctic Orogen in Dronning Maud Land - Ruppel, Antonia; Läufer, Andreas; Jacobs, Joachim; Elburg, M; Krohne, N; Eagles, Graeme; Mieth, Matthias; Jokat, Wilfried; Damaske, Detlef; Lisker, Frank ([German Society for Polar Research], 2015)
The geology of Sør Rondane has been the focus of intense research and occupies a key position for reconstructing the late Neoproterozoic to early Paleozoic geodynamic evolution in eastern Dronning Maud Land (DML). Sør Rondane appears to be located close to the supposed intersection of the East African-Antarctic Orogen (EAAO) and the Kuunga Orogen. The western part of Sør Rondane is subdivided in two distinct terranes. The amphibolite to granulite-facies NE terrane is mainly composed of metasupracrustal rocks, with detrital zircon ages in part younger than 750 Ma, deposited on older basement of unknown, possibly Rayner-type, crust (Shiraishi et al., 2008). Metamorphism has been dated by U-Pb on zircon at ca. 640-600 Ma and amphibolite-facies retrogression dated at ca. 590-530 Ma. The SW terrane is subdivided by the Main Shear Zone (MSZ) into two lithothectonic units, i.e. Pan- African greenschist- to granulite-facies metamorphic rocks with “East African” affinities in the N and a Rayner-age early Neoproterozoic gabbro-tonalite-trondhjemite-granodiorite (GTTG) complex with “Indo-Antarctic” affinities in the S. The GTTG complex has suffered Pan-African greenschist- to lower amphibolite-facies thermal overprint, but also contains large domains with only weak deformation except for its northern margin close to the MSZ. The deformation there is related to high shear strain along this structure. New zircon crystallisation ages of the GTTG cluster around 1000-930 Ma. It is interpreted to have formed along a juvenile oceanic arc, in which the wide age range might indicate a long-lasting accretionary orogen. The MSZ is characterized by a right-lateral sense of movement and high-strain ductile deformation under peak amphibolite-facies conditions. The structure can be traced over a distance of ca. 120 km between Lågkollane in the W and Lunckeryggen in the E and reaches several hundred meters in width. The MSZ cannot be traced further to the W where it seems to terminate at the north-eastern border of the NW-SE oriented prominent magnetically defined SE DML Province. The north-eastern border zone may coincide with a significant dextral shear zone that runs from the Schirmacher Oasis into the region S of Sør Rondane (Schirmacher- Rondane Lineament). The SE DML Province most likely consists of Rayner-age (1000-900 Ma) crust with evidence of intense Pan-African reworking indicated by new geochronological data and was part of a large Tonian Oceanic Arc Super Terrane (TOAST). The continuation of the MSZ into eastern Sør Rondane and beyond is not clear either, since it appears to terminate at a N-S oriented region with low magnetic signatures (central Sør Rondane corridor) that is possibly related to extensional tectonics. Crosscutting relationships with dated magmatic rocks bracket the activity of the MSZ between Latest Ediacaran to Cambrian times (c. 560- 530 Ma). Based on new combined aeromagnetic and structural results from a four-seasons survey of the greater Sør Rondane region, we propose that the crustal structural architecture of eastern DML and is strongly influenced by N-directed (with Africa/Antarctica restored to its original position in Gondwana) lateral extrusion of the EAAO. This process was likely driven by the combination of (i) indentation of the SE DML block towards the conjugate stable Kalahari- Grunehogna cratonic foreland, (ii) extensional collapse of the previously (c. 580-550 Ma) thickened and gravitational instable crust of central DML, and (iii) large-scale tectonic escape of crustal blocks in eastern DML along major shear zones such as the Schirmacher Rondane Lineament and MSZ towards an unconstrained yet unknown region at a lateral position of the EAAO.
Keywords: Dronning Maud Land; geologi

Norske interesser og politikk for Bouvetøya - [s.n.] (Melding til Stortinget, 2015)
Helt siden Bouvetøya ble norsk biland i 1930 har denne øya langt sør i Atlanterhavet vært del av vår polare identitet og historie. Gjennom tidene har øya likevel ikke vært gjenstand for stor oppmerksomhet. Siden 1930 har det heller ikke vært gitt noen samlet omtale til Stortinget av forhold som angår forvaltningen av dette området. Regjeringen mener det nå er tid for å gjøre Bouvetøya bedre kjent gjennom en melding til Stortinget. Denne meldingen har derfor som mål å beskrive Bouvetøya, og gi en bred fremstilling av ulike forhold når det gjelder rettslige rammebetingelser, forvaltning og aktivitet på øya og i havområdene rundt. Regjeringen fremmer også en melding til Stortinget som omhandler norske interesser og politikk i Antarktis, herunder de norske bilandene Dronning Maud Land og Peter I Øy, heretter omtalt som Antarktismeldingen. 1 Tradisjonelt har de tre bilandene Bouvetøya, Dronning Maud Land og Peter I Øy vært omtalt sammen. Bouvetøya ligger nord for Antarktistraktatens virkeområde, og er ubestridt norsk territorium. Regjeringen har derfor funnet det hensiktsmessig å legge frem en egen melding om norske interesser og politikk for Bouvetøya. Spørsmål som gjelder Bouvetøya håndteres som en integrert del av norsk politikk. Dette inne- bærer å gjøre norsk lovgivning gjeldende for øya i den grad det er hensiktsmessig, og å sørge for at lovgrunnlaget er tilpasset behovene. I denne meldingen om Bouvetøya beskrives intern lovgivning så vel som det folkerettslige rammeverket, og ret- tighetene og pliktene som følger av dette, herunder retten til naturressurser og plikten til å ta vare på miljøet. Det gis en egen omtale av de stats- rettslige sidene ved øya, og av at det vil bli vurdert om disse og andre forhold bør reguleres i en egen lov.
Keywords: Bouvetøya; forvaltning; lovgivning; overvåking; politikk; økonomi

Review of the low-temperature thermochronological data from the Dronning Maud Land Mountains, East Antarctica - Sirevaag, Hallgeir; Jacobs, Joachim; Ksienzyk, Anna Katharina; Dunkl, István (Norsk Geologisk Forening (NGF), 2015)
The paleo-topography of East Antarctica is highly relevant for the development of the East Antarctic ice-sheet. This ice-sheet originated probably as small ice caps and in the elevated areas of the cratons in East Antarctica around the Eocene/Oligocene boundary. East Antarctica contains three mountain ranges: the latitudinal Dronning Maud Land Mountains (DML), the longitudinal Transantarctic Mountains (TAM) and the sub-glacial Gamburtsev Mountains (GM). The 1500 km long, coast-parallel Dronning Maud Land Mountains probably resulted in a significant amount of precipitation prior to the initiation of the 34 Ma glaciation history of East Antarctica. Thus, the paleo-topography should be used as an important input parameter for the glaciation history.
Keywords: Dronning Maud Land; geologi

The significance of petroleum for the South Pole expeditions 1910-1912 - Skarung, Per (The Fram Museum, 2015)
"Inclement weather and lack of fuel was the cause of their deaths".
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; polarhistorie

Polare strøk. Skippere og fangstfolk. Den nye tid - Aasheim, Stein P. (Norske eventyrere, 2014)
Keywords: Antarktis; Bernt Balchen; Carl Anton Larsen; Carsten Borchgrevink; Nordmenn; Tryggve Gran; geografi; historie; oppdagelsesreiser; polarekspedisjoner

Hiihtovaellus etelänavalle : eräretki Roald Amundsenin jäljissä - Aasheim, Stein P; Paarma, Susanna (Gummerus, 2014)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; reiser; reiseskildringer; skisport

[Bir kəşfiyyatçı kimi həyatım] - Amundsen, Roald (Alatoran, 2014)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

Inspeksjonsordningen under Antarktistraktaten - Bech, Jon (Polarboken, 2014)
Keywords: Antarktis; jus; politikk

Kanten av isødet - Blackadder, Jesse; Berg, Ellen Karine (Juritzen, 2014)
Roman om tre kvinner fra Sandefjord og kampen om å komme først til Antarktis. Sandefjord 1930. Ingrid er gift med byens hvalkonge, Lars Christiansen. Hun har drømt om å reise til Antarktis siden hun var barn, og nå har ektemannen lovet å ta henne med på en av hvalbåtene. Betingelsen er at hun har med seg en kvinnelig ledsager, og den deprimerte enken Mathilde blir motvillig rekruttert. Samtidig sitter Lillemor Rachlew i London og ønsker mest av alt å bli første kvinne i Antarktis. Hun får høre om reisen til Ingrid, og får lurt seg med på samme båt rett før den forlater Cape Town. Kappløpet mot et livsfarlig isøde er i gang, og reisen vil bli skjebnesvanger for alle de tre kvinnene. Denne fascinerende romanen er basert på virkelige hendelser. Vi blir tatt med til 1930-årenes Sandefjord, til hvalfangstindustriens gullalder, og blir kjent med tre kvinner som kjempet ikke bare for sin selvstendighet, men også for sin plass i historien.
Keywords: Antarktis; Nordmenn; ekspedisjoner; fortellinger; kvinner; oppdagelsesreiser

Transition of flow regime along a marine-terminating outlet glacier in East Antarctica - Callens, Denis; Matsuoka, Kenichi; Steinhage, Daniel; Smith, Benjamin; Witrant, E; Pattyn, Frank (The Cryosphere, 2014)
We present results of a multi-methodological approach to characterize the flow regime of West Ragnhild Glacier, the widest glacier in Dronning Maud Land, Antarctica. A new airborne radar survey points to substantially thicker ice (>2000 m) than previously thought. With a discharge estimate of 13–14 Gt yr−1, West Ragnhild Glacier thus becomes of the three major outlet glaciers in Dronning Maud Land. Its bed topography is distinct between the upstream and downstream section: in the downstream section (<65 km upstream of the grounding line), the glacier overlies a wide and flat basin well below the sea level, while the upstream region is more mountainous. Spectral analysis of the bed topography also reveals this clear contrast and suggests that the downstream area is sediment covered. Furthermore, bed-returned power varies by 30 dB within 20 km near the bed flatness transition, suggesting that the water content at bed/ice interface increases over a short distance downstream, hence pointing to water-rich sediment. Ice flow speed observed in the downstream part of the glacier (~250 m yr−1) can only be explained through very low basal friction, leading to a substantial amount of basal sliding in the downstream 65 km of the glacier. All the above lines of evidence (sediment bed, wetness and basal motion) and the relatively flat grounding zone give the potential for West Ragnhild Glacier to be more sensitive to external forcing compared to other major outlet glaciers in this region, which are more stable due to their bed geometry (e.g. Shirase Glacier).
Keywords: Dronning Maud Land; glasiologi

Commonness and rarity in the marine biosphere - Connolly, Sean R; MacNeil, M Aaron; Caley, M Julian; Knowlton, Nancy; Cripps, Ed; Hisano, Mizue; Thibaut, Loïc M; Bhattacharya, Bhaskar D; Benedetti-Cecchi, Lisandro; Brainard, Russell E; Brandt, Angelika; Bulleri, Fabio; et al. (Proceedings of the National Academy of Sciences, 2014)
Tests of biodiversity theory have been controversial partly because alternative formulations of the same theory seemingly yield different conclusions. This has been a particular challenge for neutral theory, which has dominated tests of biodiversity theory over the last decade. Neutral theory attributes differences in species abundances to chance variation in individuals’ fates, rather than differences in species traits. By identifying common features of different neutral models, we conduct a uniquely robust test of neutral theory across a global dataset of marine assemblages. Consistently, abundances vary more among species than neutral theory predicts, challenging the hypothesis that community dynamics are approximately neutral, and implicating species differences as a key driver of community structure in nature.Explaining patterns of commonness and rarity is fundamental for understanding and managing biodiversity. Consequently, a key test of biodiversity theory has been how well ecological models reproduce empirical distributions of species abundances. However, ecological models with very different assumptions can predict similar species abundance distributions, whereas models with similar assumptions may generate very different predictions. This complicates inferring processes driving community structure from model fits to data. Here, we use an approximation that captures common features of “neutral” biodiversity models—which assume ecological equivalence of species—to test whether neutrality is consistent with patterns of commonness and rarity in the marine biosphere. We do this by analyzing 1,185 species abundance distributions from 14 marine ecosystems ranging from intertidal habitats to abyssal depths, and from the tropics to polar regions. Neutrality performs substantially worse than a classical nonneutral alternative: empirical data consistently show greater heterogeneity of species abundances than expected under neutrality. Poor performance of neutral theory is driven by its consistent inability to capture the dominance of the communities’ most-abundant species. Previous tests showing poor performance of a neutral model for a particular system often have been followed by controversy about whether an alternative formulation of neutral theory could explain the data after all. However, our approach focuses on common features of neutral models, revealing discrepancies with a broad range of empirical abundance distributions. These findings highlight the need for biodiversity theory in which ecological differences among species, such as niche differences and demographic trade-offs, play a central role.
Keywords: Sørishavet; biodiversitet; biologi; marin økologi; marine økosystemer; polarområdene; zoologi

Annual cycle of Antarctic Baseline Aerosol: A Benchmark for Natural Aerosol Processes - Fiebig, Markus; Hirdman, David; Lunder, Chris R; Ogren, John A; Solberg, Sverre; Thompson, Rona L; Stohl, Andreas (2014)
An ongoing challenge in attributing anthropogenic climate change is to distinguish anthropogenic and natural changes of atmospheric composition, e.g. concerning atmospheric aerosol and its climate effects. Aerosol properties measured at pristine locations, to the extend they still exist, can serve as a climate model benchmark for verifying the representation of natural aerosol processes in the model.
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; klimaendringer; klimamodeller

Commercial fishing vessel as research vessels in the Antarctic – Requirements and solutions exemplified with a new vessel - Godø, Olav; Reiss, Christian; Siegel, V; Watkins, Jonathan (CCAMLR science journal of the Scientific Committee and the Commission for the Conservation of Antarctic Marine Living Resources, 2014)
Keywords: Antarktis; fiskefartøy; forskning; forskningsfartøy; klimaendringer; oseanografi; økosystem

Comparative study on PCDD/F pollution in soil from the Antarctic, Arctic and Tibetan Plateau - Jia, Shenglan; Wang, Qiang; Li, Li; Fang, Xuekun; Shi, Yehong; Xu, Weiguang; Hu, Jianxin (Science of the Total Environment, 2014)
The concentrations of polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) in 35 soil samples collected from Fildes Peninsula in the Antarctic, Ny-Ålesund in the Arctic, and Zhangmu-Nyalam in the Tibetan Plateau were reported in this study. A comparison of the total concentration and TEQ of PCDD/Fs at the Three Poles was conducted. Both the total concentration and TEQ of PCDD/Fs demonstrates a decreasing trend in the order of Zhangmu-Nyalam (mean: 26.22 pg/g, 0.37 pg I-TEQ/g)>Ny-Ålesund (mean: 9.97 pg/g, 0.33 pg I-TEQ/g)>Fildes Peninsula (mean: 2.18 pg/g, 0.015 pg I-TEQ/g) (p<0.05). In all samples, the congener and homologue profiles dominated with higher (seven and eight) chlorinated PCDD/Fs (more than 85% of the total mass percentage of PCDD/Fs) at the Three Poles. Finally, a FLEXPART backward simulation was used to preliminarily identify the potential local and regional anthropogenic sources of PCDD/Fs. The results imply that the air masses passing over surrounding regions with significant PCDD/F emissions might contribute to the occurrence of PCDD/Fs in both the Arctic and Tibetan Plateau.
Keywords: Antarktis; menneskelig påvirkning; miljøgifter; miljøovervåking; polarområdene

The Third Expedition, 1910-1912: Antarctica and the Southern Ocean - Johnson, Charles W (Ice ship : the epic voyages of the polar adventurer Fram, 2014)
Keywords: Antarktis; Fram (skip); Roald Amundsen; Sydpolsekspedisjonen; Sørpolen; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner

Fjerning av reinsdyr på Sør-Georgia: nok et avsluttet kapittel i norsk hvalfangsthistorie - Kilander, Carl Erik (Polarboken, 2014)
Keywords: Sørishavet; zoologi; økologi

Et besøk på Bettyfjellet - Kristensen, Monica; McIntyre, Neil (Polarboken, 2014)
Keywords: Antarktis; ekspedisjoner; historie

High variability of climate and surface mass balance induced by Antarctic ice rises - Lenaerts, Jan T M; Joel, Brown.; Van Den Broeke, Michiel R; Matsuoka, Kenichi; Drews, Reinhard; Callens, Denis; Philippe, Morgane; Gorodetskaya, Irina V; Van Meijgaard, Erik; Reijmer, Carleen H; Pattyn, Frank; Van Lipzig, Nicole P M (Journal of Glaciology, 2014)
Ice rises play key roles in buttressing the neighbouring ice shelves and potentially provide palaeoclimate proxies from ice cores drilled near their divides. Little is known, however, about their influence on local climate and surface mass balance (SMB). Here we combine 12 years (2001–12) of regional atmospheric climate model (RACMO2) output at high horizontal resolution (5.5 km) with recent observations from weather stations, ground-penetrating radar and firn cores in coastal Dronning Maud Land, East Antarctica, to describe climate and SMB variations around ice rises. We demonstrate strong spatial variability of climate and SMB in the vicinity of ice rises, in contrast to flat ice shelves, where they are relatively homogeneous. Despite their higher elevation, ice rises are characterized by higher winter temperatures compared with the flat ice shelf. Ice rises strongly influence SMB patterns, mainly through orographic uplift of moist air on the upwind slopes. Besides precipitation, drifting snow contributes significantly to the ice-rise SMB. The findings reported here may aid in selecting a representative location for ice coring on ice rises, and allow better constraint of local ice-rise as well as regional ice-shelf mass balance.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; klima

Post-breeding at-sea movements of three central-place foragers in relation to submesoscale fronts in the Southern Ocean around Bouvetøya - Lowther, Andrew D; Lydersen, Christian; Biuw, Martin; de Bruyn, P J Nico; Hofmeyr, Greg J G; Kovacs, Kit M (Antarctic Science, 2014)
Keywords: Bouvetøya; oseanografi; pelsseler; pingviner; satellitt; telemetri

Å filme de dypfrosne hemmelighetene til en aktiv vulkan - Roberts, Jason (Polarboken, 2014)
Keywords: Antarktis; film; geofysikk; vulkaner

Norge i Antarktis - Rognhaug, Magnus Hovind (red.) (Norsk Polarinstitutt, 2014)
Keywords: Antarktis; Antarktistraktaten; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Sørishavet; forskning; miljøvern; polarforskning; politikk

Future challenges in environmental management of National Antarctic Programs - Sánchez, Rodolfo Andrés; Njåstad, Birgit (Antarctic futures : human engagement with the Antarctic environment, 2014)
Keywords: Antarktis; miljøvern

Hvalfangerkirken i Grytviken 100 år - Tokstad, Kjell (Polarboken, 2014)
Keywords: Sørishavet; bygninger; historie

Thick-shelled, grazer-protected diatoms decouple ocean carbon and silicon cycles in the iron-limited Antarctic Circumpolar Current - Assmy, Philipp; Smetacek, Victor; Montresor, Marina; Klaas, Christine; Henjes, Joachim; Strass, Volker; Arrieta, Jesus M; Bathmann, Ulrich; Berg, Gry Mine; Breitbarth, Eike; Cisewski, Boris; Friedrichs, Lars; et al. (Proceedings of the National Academy of Sciences, 2013)
Diatoméer – alger med skall av silisium, som er helt avhengige av næringsstoffet silikat – dominerer fytoplankton oppblomstringer og spiller en nøkkelrolle i havets økosystemer og i global karbonsyklus. Vi viser hvordan forskjeller i økologiske karakteristikker av dominerende arter i Sørishavet, som ble observert under det in situ europeiske jerngjødslings eksperimentet (European Iron Fertilization Experiment - EIFEX), kan påvirke karbon og silisium syklusene i havet. Vi argumenterer for at økologien til tykkskallete diatomé arter, som er selektert for av sterk beiting fra kopepoder, tar opp silikat fremfor andre næringsstoffer i det dype Sørishavet og underliggende sedimenter. Fordi Sørishavet er en viktig sentral for oseanisk fordeling av næringsstoffer, selektivt opptak av silikat i dette havområdet begrenser oppblomstringene av diatoméer i andre deler av verdenshavene, noe som potensielt får konsekvenser for biotisk opptak av karbon i hele verdens havområder.
Keywords: Sørishavet; marinbiologi; oseanografi; plankton; økosystem

Antarktis-isen: større og dypere - Bjermeland, Monica (Klima: norsk magasin for klimaforskning, 2013)
De siste tiårene har isen i Antarktis økt litt i utbredelse. Men ikke fordi det er blitt kaldere der.
Keywords: Antarktis; Sørishavet; glasiologi; havis; is; klima

Women, whales and Antarctica - Blackadder, Jesse (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Antarktis; første landgang; historie; kvinner; oppdagelsesreiser

Did a Dutch company kill whales with tax payers' money after world war II? - Bruijn, Jaap R; Schokkenbroek, Joost C A (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Nordmenn; Sørishavet; historie; hvalfangst; pelagisk; sjøfolk

Genetic characterization and life cycle of the diatom Fragilariopsis kerguelensis - Fuchs, Nike; Scalco, Eleonora; Kooistra, Wiebe; Assmy, Philipp; Montresor, Marina (European Journal of Phycology, 2013)
Diatoméen Fragilariopsis kerguelensis fra Sørishavet spiller en nøkkelrolle i marin silisium syklus fordi restene av celleveggene synker til havbunnen rundt Antarktis, hvor de bygger opp de største depotene av biologisk generert silisium i verden. Tomme skall av diatomeer har også blitt brukt som indikatorer/proksier for produksjonsregimer i geologisk fortid av mikro-paleontologer. For å bedre kunne beskrive og forstå biologien av denne arten fra Sørishavet har vi adressert dens genetiske identitet ved hjelp av molekylære markører, og for første gang vært i stand til å anslå kjønn til denne arten. Dette har ført til at vi har vært i stand til å kjøre et stort antall vellykkede parringseksperimenter. Vi har vært i stand til å avdekke det intrikate parringssystemet og livssyklus karakteristikker til F. kerguelensis og demonstrere at vi kun har å gjøre med én biologisk art. En bedre forståelse av livssyklus til F. kerguelensis burde hjelpe for tolkning av geologiske tidsserier for denne arten og belyse rollen miljøfaktorer kan ha for å regulere populasjoner av arten.
Keywords: Sørishavet; genetikk; marinbiologi; plankton

Oral sources at the whaling museum: from speech to text and exhibition - Garmel, Hanne (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Nordmenn; Sørishavet; erindringer; hvalfangst; museer; pelagisk

Tre kilder til smelting av Fimbulisen - Hattermann, Tore; Nøst, Ole A; Smedsrud, Lars H (Klima: norsk magasin for klimaforskning, 2013)
Soloppvarmet overflatevann er en sentral varmekilde som bidrar til smelting av isbremmen Fimbulisen i Dronning Maud Land.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; klima

Neoproterozoic/Lower Palaeozoic geodynamic evolution of Dronning Maud Land: integrating geology and geophysics - Jacobs, Joachim; Läufer, Andreas; Clark, Chris; Kleinhanns, Ilka; Elburg, Marlina; Ruppel, Antonia; Estrada, Solveig; Damaske, Detlef; Jokat, Wilfried; Riedel, Sven; Lucka, Nicole (Changing polar regions : 25th International Congress on Polar Research ; March 17-22, 2013, Hamburg, Germany, 2013)
East Antarctica probably formed by amalgamation of a number of cratons along distinct Ediacaran mobile belts, including the ca. 600-500 Ma East African-Antarctic Orogen (EAAO) that dissects Dronning Maud Land (DML). New field-work during the international expeditions Geodynamic Evolution of East Antarctica (GEA) I + II in the austral summers 2010/11 and 2011/12, and first geochronological results from eastern DML reveal a complex tectonic architecture across the belt. In western DML, the EAAO reworks older Mesoproterozoic crust of the Maud Belt; the westernmost boundary of the mobile belt is characterized by a major dextral transpressional shear zone. In central DML, a major magnetic anomaly, the Forster anomaly, was interpreted as a cryptic suture of the EAAO (Riedel et al. 2012). The area where the Forster anomaly crosses the DML mountains is poorly investigated so far, but appears to coincide with a major strike slip shear zone in the southern Kurze Mts. and the occurrence of major Ediacaran granulite bodies. East of the Forster anomaly, the magnetic anomaly pattern changes significantly and typical Maud type crust is not present any longer. GEA II targeted a range of nunataks between Sør Rondane and central DML that had never been visited previously (from Blåklettane and Bergekongen in the E to Urna and Sørsteinen in the W). These nunataks are dominated by medium- to high-grade metasedimentary and metavolcanic rocks of possibly Neoproterozoic age, including abundant marble and graphite schists. Sør Rondane in eastern DML, is dominated by two distinct blocks separated by the dextral Main Shear Zone. The northwestern block is still part of the eastern EAAO, where new SHRIMP zircon data from metamorphic rims provide ages of ca. 560 Ma. The southeastern block is made up of a TTG terrane, which provides four new SHRIMP zircon dates between 990-980 Ma, interpreted as igneous crystallization ages (oceanic arc). The TTG terrane shows limited tectonic overprint and is likely the southeastern foreland of the EAAO. Close to the contact of the two blocks grey geisses and augen-gneisses gave zircon crystallization ages of ca. 750 Ma, ages which were previously unknown from the EAAO. The Forster anomaly therefore separates distinctly different parts of the EAAO: a) a reworked, mainly Grenville-age crust to the W (the overprinted margin of the Kalahari Craton) and b) a part of the orogen dominated by Neoproterozoic accretionary tectonics to the E. This difference is also reflected in the geochemistry of voluminous late-tectonics granitoids across the belt.
Keywords: Dronning Maud Land; geofysikk; geologi

Proterozoic Evolution of Central Dronning Maud Land (East Antarctica) from Rodinia to Gondwana - Jacobs, Joachim; Läufer, Andreas; Clark, Chris; Kleinhanns, Ilka; Elburg, Marlina; Ruppel, Antonia; Estrada, Solveig; Damaske, Detlef; Jokat, Wilfried; Riedel, Sven; Lucka, Nicole (Geochemical Society and of the European Association of Geochemistry, 2013)
Central Dronning Maud Land (CDML) in East Antarctica is an important region for understanding Rodinia and Gondwana supercontinent cycles. Zircon U-Pb dating and Hf-O isotopic data revealed by extensive sampling across CDML provide constraints on the timing and source of main magmatism and new insights into the crustal composition and evolution. SIMS zircon U-Pb ages indicate multi-stage magmatic activities from Mesoproterozoic to Cambrian times at 1160-1130 Ma, 1115-1100 Ma, 1090-1070 Ma, 780-750 Ma, 645-600 Ma and 530-485 Ma, as well as Mesoproterozoic metamorphism at 1085-1050 Ma recorded by zircon rims. This region was subjected a large-scale and long-lasting high-grade metamorphism during 600-500 Ma. Most 1160-1080 Ma granitic rocks exhibit εHf (t) values ranging from +5 and +8 and δ18O slightly higher than mantle value (6-7 ‰), indicating a main derivation from juvenile crust. The involvement of Paleoproterozoic continental materials, which were most likely from adjacent Kalahari Craton, is attested by minor samples with negative to neutral εHf (t) and significantly elevated δ18O values (8-10 ‰). The late Neoproterozoic (750-600 Ma) rocks, including anorthosite, charnockite and granite, display an evolved Hf isotopic composition and high δ18O values (7.5-9 ‰), suggesting a significant addition of crust-derived materials into the source. The data imply that in CDML, late Mesoproterozoic (Grenville-age) magmatism during the assembly of Rodinia is dominated by the addition of new crust with subordinate reworking of ancient crust. Subsequent subduction process associated with the break-up of Rodinia and assembly of Gondwana largely witnessed recycling of previous continental components. Combined with whole-rock geochemistry, it is speculated that the accretionary process along the Maud margin of Kalahari Craton lasted from the Mesoproterozoic, across the late Tonian (750 Ma) until Ediacaran to suture west and east Gondwana blocks.
Keywords: Dronning Maud Land; geokjemi; geologi

Cetus soveticus: exotic and collective cultures of Soviet whaling within the 1960s - Jones, Ryan Tucker (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Nordmenn; Sørishavet; hvalfangst; pelagisk

Bouvetøya : a cultural history of an isolated landmass - Mathews, Freddy Dewe (Freddy Dewe Mathews, 2013)
Keywords: Bouvetøya; historie; kultur

Whaling, lobbying and politics - Ringstad, Jan Erik (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalindustri; pelagisk; politikk

The friend who outstayed his welcome? Johan Hjort and the difficulties of bringing science to bear upon whaling - Roberts, Peder (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Sørishavet; fiskeripolitikk; forskning; hvalbestanden; hvalfangst; pelagisk

De flytende kokeriene : telegraf - Willem Barendsz (II) - Røsset, Geir; Rae, Jim; Basberg, Bjørn L (Novus, 2013)
Denne boken viser med tekst og bilder utviklingen av hvalkokeriene fra de første dampskipene ble ombygget like etter 1900. Den viser hvordan det i mange år fortsatt også ble brukt seilskip, og hvordan skipene gradvis ble større og bedre utrustet. Gradvis ble de til «flytende fabrikker».
Keywords: Sørishavet; fangstfartøyer; historie; hvalbåter; hvalfangstindustri; hvalfangstskip; hvalindustri; hvalkokerier; pelagisk

Sydpolfarerne Per Savio og Ole Must : liv i grenseland - Sandholm, Unni Aas (Temahefter Aas Sandholm, 2013)
Keywords: Antarktis; Southern Cross; Sydpolen; ekspedisjonen; oppdagelsesreiser; overvintring; polarekspedisjoner; samer

Tryggve Gran : is, luft og krig - Simonsen, Anne Hege (Cappelen Damm, 2013)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; biografier; ekspedisjoner; oppdagelsesreiser; polarområdene

Da Norge annekterte Bouvetøya - Skagestad, Odd Gunnar (Historie (Bergen), 2013)
Keywords: Bouvetøya; historie; politikk

Hvordan Bouvetøya ble norsk - Skagestad, Odd Gunnar (UD-posten: husorgan for utenrikstjenesten, 2013)
Keywords: Bouvetøya; historie; politikk

Vår sydligste provins: Dronning Maud Land 75 år - Skagestad, Odd Gunnar (Historie (Bergen), 2013)
Keywords: Dronning Maud Land; historie; politikk

I Roald Amundsens skispor : kappløpet til Sørpolen - 100 år etter - Aasheim, Stein P (Cappelen Damm, 2012)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; reiser; reiseskildringer; skisport

Den japanske antarktisekspedisjonen i 1912 - Barr, Susan (Polarboken, 2012)
Keywords: Antarktis; ekspedisjoner; historie

The state of the poles : climate lessons from the International Polar Year - Bjørnæs, Christian; Prestrud, Pål (Unipub, 2012)
Keywords: Antarktis; klimaendringer; polarforskning; polarområdene

Roald Amundsen: Forsker eller grobian? - Blix, Arnoldus Schytte (Nordisk tidskrift för vetenskap, konst och industri, 2012)
Roald Amundsens (1872-1928) liv og bedrifter er fremstilt i en rekke biografier, men det er oppdageren og eventyreren som blir tillagt mest vekt, mens vitenskapsmannen og forskeren tidvis underkjennes. Professor i arktisk biologi ved Universitetet i Tromsø, Arnoldus Schytte Blix, er kritisk til mye av det biografiske arbeidet som er gjort, og mener det er et åpent spørsmål om kontorhistorikere og journalister har noen reell mulighet til fullt ut å forstå Roald Amundsens situasjon og reaksjoner. Artikkelen er basert på et foredrag med en rekke illustrasjoner i Det Norske Videnskabs-Akademi, 17. november 2011.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; biografier; oppdagelsesreiser

Til Sydpolen - 100 år etter - Johansen, Asle T; Grindhaug, Gaute; Berg, Agnar (Fri flyt, 2012)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; reiser; reiseskildringer; skisport

The South Pole expedition of Roald Amundsen: how did he prepare for the expedition and what do his crewmembers' diaries tell us about it? / Geir O. Kløver. - Kløver, Geir Olav (Nimrod : the Journal of the Ernest Shackleton Autumn School, 2012)
Describes Amundsen's experience on de Gerlache's 1897-99 Belgica Antarctic expedition, scientific interests, lessons learned on his 1903-06 Gjøa Northwest Passage expedition, and experience on 1910-12 Fram Antarctic expedition. Gives details of crew members on Antarctic expedition with account of their diaries. Author is director of Fram Museum and editor of South Pole diaries of Amundsen and fourteen of his crew members.
Keywords: Antarktis; Belgica ekspedisjon; Sydpolsekspedisjonen; dagbøker; polarhistorie

Antarctic krill swarm characteristics in the Southeast Atlantic sector of the Southern Ocean - Krafft, Bjørn A.; Skaret, Georg; Knutsen, Tor; Melle, Webjørn; Klevjer, Thor; Søiland, Henrik (Marine ecology. Progress series, 2012)
Knowledge about swarm dynamics and underlying causes is essential to understand the ecology and distribution of Antarctic krill . We collected acoustic data and key environmental data continuously across extensive gradients in the little-studied Southeast Atlantic sector of the Southern Ocean. A total of 4791 krill swarms with swarm descriptors including swarm height and length, packing density, swimming depth and inter-swarm distance were extracted. Through multivariate statistics, swarms were categorized into 4 groups. Group 2 swarms were largest (median length 108 m and thickness 18 m), whereas swarms in both Groups 1 and 4 were on average small, but differed markedly in depth distribution (median: 52 m for Group 1 vs. 133 m for Group 4). There was a strong spatial autocorrelation in the occurrence of swarms, and an autologistic regression model found no prediction of swarm occurrence from environmental variables for any of the Groups 1, 2 or 4. Probability of occurrence of Group 3 swarms, however, increased with increasing depth and temperature. Group 3 was the most distinctive swarm group with an order of magnitude higher packing density (median: 226 ind. m ) than swarms from any of the other groups and about twice the distance to nearest neighbor swarm (median: 493 m). The majority of the krill were present in Group 3 swarms, and the absence of association with hydrographic or topographic concentrating mechanisms strongly suggests that these swarms aggregate through their own locomotion, possibly associated with migration.
Keywords: Bouvetøya; Sørishavet; datainnsamling; ekkolodd; krill; marin biologi; plankton; økologi

Antarktis - Langerud, Per Jan (Klima, is og forskerfeil, 2012)
Keywords: Antarktis; klimaendringer; klimaforskning

Radar characterization of the basal interface across the grounding zone of an ice-rise promontory in East Antarctica - Matsuoka, Kenichi; Pattyn, Frank; Callens, Denis; Conway, Howard (Annals of Glaciology, 2012)
Radar power returned from the basal interface along a 42 km long profile over an ice-rise promontory and the adjacent Roi Baudouin ice shelf, Dronning Maud Land, East Antarctica, is analyzed to infer spatial variations in basal reflectivity and hence the basal environment. Extracting basal reflectivity from basal returned power requires an englacial attenuation model. We estimate attenuation in two ways: (1) using a temperature-dependent model with input from thermomechanical ice-flow models; and (2) using a radar method that linearly approximates the geometrically corrected returned power with ice thickness. The two methods give different results. We argue that attenuation calculated using a modeled temperature profile is more robust than the widely used radar method, especially in locations where depth-averaged attenuation varies spatially or where the patterns of basal reflectivity correlate with the patterns of the ice thickness.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

The Mapping of Antarctica - Pedersen, Jakob Søndergård; Curtis, Philip (The Map House, 2012)
Keywords: Antarktis; ekspedisjoner; kart; kartlegging; kartografi; oppdagelsesreiser

Cecilie Skog. Liv Arnesen. Monica Kristensen - Sandberg, Sigri (Polarheltinner : Cecilie Skog, Liv Arnesen, Monica Kristensen, Christiane Ritter, Wanny Woldstad, Ellen Dorthea Nøis, Hanna Resvoll-Holmsen, 2012)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjoner; biografier; friluftsliv; kvinner; polarekspedisjoner; polarhistorie

Extent of low-accumulation 'wind glaze' areas on the East Antarctic plateau: implications for continental ice mass balance - Scambos, Ted A; Frezzotti, Massimo; Haran, T; Bohlander, J; Lenaerts, Jan T M; Van Den Broeke, M R; Jezek, K; Long, D; Urbini, S; Farness, K; Neumann., T; Albert, M; et al. (Journal of Glaciology, 2012)
Persistent katabatic winds form widely distributed localized areas of near-zero net surface accumulation on the East Antarctic ice sheet (EAIS) plateau. These areas have been called 'glaze' surfaces due to their polished appearance. They are typically 2-200 km2 in area and are found on leeward slopes of ice-sheet undulations and megadunes. Adjacent, leeward high-accumulation regions (isolated dunes) are generally smaller and do not compensate for the local low in surface mass balance (SMB). We use a combination of satellite remote sensing and field-gathered datasets to map the extent of wind glaze in the EAIS above 1500 m elevation. Mapping criteria are derived from distinctive surface and subsurface characteristics of glaze areas resulting from many years of intense annual temperature cycling without significant burial. Our results show that 11.2 ± 1.7%, or 950 ± 143 × 103km2, of the EAIS above 1500 m is wind glaze. Studies of SMB interpolate values across glaze regions, leading to overestimates of net mass input. Using our derived wind-glaze extent, we estimate this excess in three recent models of Antarctic SMB at 46-82 Gt. The lowest-input model appears to best match the mean in regions of extensive wind glaze.
Keywords: Antarktis; glasiologi

Nansen-Amundsen-året 2011 - Schreuder, Janne (ed.); Jaklin, Gunn Sissel (ed.) (Norsk Polarinstitutt, 2012)
Keywords: Antarktis; Roald Amundsen; jubileer; polarområdene

Sydpolen eller Sørpolen? - Skagestad, Odd Gunnar (Ordet: kvartalsskrift for riksmålsbevegelsen, 2012)
Keywords: Antarktis; språk; stedsnavn

Virvler øker smeltingen - Smedsrud, Lars H; Biuw, Martin; Tverberg, Vigdis; Lydersen, Christian; Hattermann, Tore; Kovacs, Kit M; Nøst, Ole A (Klima: norsk magasin for klimaforskning, 2012)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; klima; oseanografi

Of reindeer, ponies and automobiles : Roald Amundsen and the Norwegian bid for the South Pole - Turney, Chris (1912 : the year the world discovered Antarctica, 2012)
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Veivisere under sydkorset - Walsøe, Jan Oskar (Sophie Borchgrevink Nordrum og Ivar O. Nordrum, 2012)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; Sydpolen; ekspedisjonen; ekspedisjoner; kartlegging; oppdagelsesreiser; polarområdene

Impact of increasing Antarctic ice-shelf melting on Southern Ocean hydrography - Wang, Caixin; Wang, Keguang (Journal of Glaciology, 2012)
Southern Ocean hydrography has undergone substantial changes in recent decades, concurrent with an increase in the rate of Antarctic ice-shelf melting (AISM). We investigate the impact of increasing AISM on hydrography through a twin numerical experiment, with and without AISM, using a global coupled sea-ice/ocean climate model. The difference between these simulations gives a qualitative understanding of the impact of increasing AISM on hydrography. It is found that increasing AISM tends to freshen the surface water, warm the intermediate and deep waters, and freshen and warm the bottom water in the Southern Ocean. Such effects are consistent with the recent observed trends, suggesting that increasing AISM is likely a significant contributor to the changes in the Southern Ocean. Our analyses indicate potential positive feedback between hydrography and AISM that would amplify the effect on both Southern Ocean hydrography and Antarctic ice-shelf loss caused by external factors such as changing Southern Hemisphere winds.
Keywords: Sørishavet; glasiologi; hydrografi

Cold recall: Roald Amundsen's reflections from the South Pole - Amundsen, Roald; Kløver, Geir O (Fram Museum, 2011)
Keywords: Antarktis; ekspedisjoner; historie

Polar settlements : location, techniques and conservation - Barr, Susan (red.); Chaplin, Paul (red.) (ICOMOS International Polar Heritage Committee, 2011)
Keywords: Antarktis; hvalfangststasjoner; kulturminnevern; polarforskning; polarområdene; turisme

Sydpolsekspedisjonen 1910-1912 - Bjaaland, Olav (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

The ANTOSTRAT Legacy: Science Collaboration and International Transparency in Potential Marine Mineral Resource Exploitation of Antarctica - Cooper, Alan; Barker, Peter; Barrett, Peter; Behrendt, John; Brancolini, Giuliano; Childs, Jonathan; Escutia, Carlota; Jokat, Wilfried; Kristoffersen, Yngve; Leitchenkov, German; Stagg, Howard; Tanahashi, Manabu; et al. (Science Diplomacy: Antarctica, Science, and the Governance of International Spaces, 2011)
Keywords: Antarktis; geopolitikk; internasjonal samarbeid; marin geologi; mineraler; ressurser; stratigrafi; tektonikk

Belgica. South Pole. The Heroic Dogs. Darkness and Light. Amundsen and Byrd - Cox, Lynne (South with the sun : Roald Amundsen, his polar explorations, and the quest for discovery, 2011)
Keywords: Antarktis; Roald Amundsen; Sydpolekspedisjonen; Sydpolen; oppdagelsesreiser; polarekspedisjoner; sledehunder

Sydpolsekspedisjonen 1910-1912 - Gjertsen, Hjalmar Fredrik (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Hassel, Sverre (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Ecosystem study and krill survey aboard G.O. Sars in Southern Ocean - Iversen, Svein A; Coulthard, Alison (International Polar Year 2007-2008 : the Norwegian contribution, 2011)
Keywords: Bouvetøya; Det Internasjonale polaråret 2007; krill; marine økosystemer; plankton; polarforskning

Sydpolsekspedisjonen 1910-1912 - Johansen, Hjalmar (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Das Eis und der Tod : Scott, Amundsen und das Drama am Südpol - Jostmann, Christian (Beck, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Der Wettlauf zum Südpol : das grösste Abenteuer der Geschichte - Knopp, Guido; Sporn, Mario; Schnier, Marten (Bertelsmann, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Seals used as "research assistants" in the polar oceans - Kovacs, Kit M; Coulthard, Alison (International Polar Year 2007-2008 : the Norwegian contribution, 2011)
Keywords: Det Internasjonale polaråret 2007; Sørishavet; polarforskning; polarområdene; seler; sjøpattedyr

Bildeberetninger. Mediebegivenheter. Polprospekter - Lund, Harald Østgaard; Berg, Siv Frøydis (Norske polarheltbilder : 1888-1928, 2011)
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolsekspedisjonen; fotografi; fotohistorie; kulturhistorie; polarekspedisjoner; polarområdene; polfarere

Race to the end : Scott, Amundsen and the South Pole - MacPhee, Ross D E (The Natural History Museum, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

På hvalfangst, 1955-56 - Mortensen, Mauritz Sundt (Atlantic Press, 2011)
Keywords: Sørishavet; hvalfangst

Sydpolsekspedisjonen 1910-1914 - Nilsen, Thorvald (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; oseanografi; polarområdene

The present location of the tent that Roald Amundsen left behind at the South Pole in December 1911 - Orheim, Olav (Polar Record, 2011)
Determining the present precise location of Amundsen's tent is a function of 1) the precision of Amundsen's navigation in 1911, 2) the flow of ice since then, and 3) the amount of burial by intervening snow fall. These factors are discussed and it is concluded that the best location that can be given for the tent in December 2011 is 89° 58′ 51″ S, 46° 14′ E, and lying 17 m below the present snow surface. The uncertainty in the position is 0.3 km, and is mainly related to uncertainties in the original positioning. It can be concluded with high certainty that the tent lies between 1.8 and 2.5 km from the South Pole.
Keywords: Antarktis; ekspedisjoner; glasiologi; historie

Le tombeau des glaces : duel mortel pour le pôle - Pierre, Marc (Dorval, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Prestrud, Kristian (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1914 - Schröer, Adolf Hermann; Hansen, Ludvig; Rønne, Martin; Hanssen, Helmer; Kutschin, Aleksandr; Wisting, Oscar; Stubberud, Jørgen; Doxrud, Christian; Stubberud, Jørgen; Hansen, Ludvig; Rønne, Martin (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Antarktis : 71 dager, 1800 kilometer og én million tanker - Skog, Cecilie; Sandberg, Sigri (Gyldendal, 2011)
Keywords: Antarktis; Sydpolen; ekspedisjoner; polarekspedisjoner; reiser; reiseskildringer

Overvåking av havklima i Antarktis - Strand, Kjersti Opstad; Østerhus, Svein; Gammelsrød, Tor (Klima : norsk magasin for klimaforskning, 2011)
Keywords: Sørishavet; global oppvarming; havnivåstigning; klimaendringer

Amundsens omstridte forløper ; Innsjøen under isen - Thuesen, Nils Petter (Vi menn vitenskap & historie, 2011)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Vostoksjøen; ekspedisjoner; glasiologi; subglasial innsjø

Clues to historical climate variation and future changes in sea level buried in the Antarctic ice (TASTE-IDEA) - Winther, Jan-Gunnar; Coulthard, Alison (International Polar Year 2007-2008 : the Norwegian contribution, 2011)
Keywords: Det Internasjonale polaråret 2007; Dronning Maud Land; glasiologi; havnivåstigning; klimaendringer; polarforskning

Sydpolsekspedisjonen 1910-1912 - Amundsen, Roald (Frammuseet, 2010)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

The South Pole expedition 1910-1912 - Amundsen, Roald (Frammuseet, 2010)
Keywords: Antarktis; Fram (skip); Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Roald Amundsens sydpolsferd (1910-1912) = Roald Amundsen's South Pole expedition (1910-1912) - Amundsen, Roald; Diesen, Jan Anders; Lund, Harald Østgaard (Norsk filminstitutt, 2010)
Keywords: Antarktis; Fram (skip); Norge; Sydpolen; Sydpolsekspedisjonen; dokumentarfilmer; ekspedisjonsfilmer; oppdagelsesreiser; polarområdene

Race for the South Pole : the expedition diaries of Scott and Amundsen - Amundsen, Roald; Scott, Robert Falcon; Bjaaland, Olav; Huntford, Roland (Continuum, 2010)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; kjeldeskrift; oppdagelsesreiser; polarområdene; polferder

Mindre snø enn forventet i Antarktis - Anschütz, Helgard; Isaksson, Elisabeth (Klima: norsk magasin for klimaforskning, 2010)
Keywords: Dronning Maud Land; glasiologi; is; klima; snø

East Antarctic snow accumulation changes - Anschütz, Helgard; Isaksson, Elisabeth; Müller, Karsten; Winther, Jan-Gunnar; Albert, Mary (Ice and climate news, 2010)
Keywords: Antarktis; glasiologi

Long-range migration of a chinstrap penguin from Bouvetøya to Montagu Island, South Sandwich Islands - Biuw, Martin; Lydersen, Christian; Nico de Bruyn, P. J.; Arriola, Aline; Hofmeyr, Greg G. J.; Kritzinger, Petrus; Kovacs, Kit M. (Antarctic Science, 2010)
We describe a long-range migration of a pre-moulting adult chinstrap penguin from Bouvetøya, a small relatively recently established colony, to the South Sandwich Islands, where large, established colonies of this species reside. The trip lasted around three weeks, covered ∼3600 km, and the time of arrival was consistent with the annual moult. The bird did not travel along the shortest path or along a constant bearing, but instead followed what appeared to be a series of two or three rhumb lines of constant bearing. Small southward and northward deviations from the general path were consistent with local water currents. Travel speeds were high during daylight but decreased at night, suggesting that resting or opportunistic feeding occurred preferentially at night. While long-range winter migrations of chinstraps to feeding areas in the vicinity of distant colonies have been previously described, this is the first observation of such a trip during the period between breeding and moulting, and the first record of an individual actually arriving at one of these distant colonies. This has implications for understanding population structure and management of this important Southern Ocean predator.
Keywords: Bouvetøya; NARE 2007/08; Sør-Sandwichøyene; marin biologi; pingviner; sjøfugler

Effects of hydrographic variability on the spatial, seasonal and diel diving patterns of southern elephant seals in the eastern Weddell Sea - Biuw, Martin; Nøst, Ole Anders; Stien, Audun; Zhou, Qianhe; Lydersen, Christian; Kovacs, Kit M (PloS One, 2010)
Weddell Sea hydrography and circulation is driven by influx of Circumpolar Deep Water (CDW) from the Antarctic Circumpolar Current (ACC) at its eastern margin. Entrainment and upwelling of this high-nutrient, oxygen-depleted water mass within the Weddell Gyre also supports the mesopelagic ecosystem within the gyre and the rich benthic community along the Antarctic shelf. We used Conductivity-Temperature-Depth Satellite Relay Data Loggers (CTD-SRDLs) to examine the importance of hydrographic variability, ice cover and season on the movements and diving behavior of southern elephant seals in the eastern Weddell Sea region during their overwinter feeding trips from Bouvetøya. We developed a model describing diving depth as a function of local time of day to account for diel variation in diving behavior. Seals feeding in pelagic ice-free waters during the summer months displayed clear diel variation, with daytime dives reaching 500-1500 m and night-time targeting of the subsurface temperature and salinity maxima characteristic of CDW around 150-300 meters. This pattern was especially clear in the Weddell Cold and Warm Regimes within the gyre, occurred in the ACC, but was absent at the Dronning Maud Land shelf region where seals fed benthically. Diel variation was almost absent in pelagic feeding areas covered by winter sea ice, where seals targeted deep layers around 500-700 meters. Thus, elephant seals appear to switch between feeding strategies when moving between oceanic regimes or in response to seasonal environmental conditions. While they are on the shelf, they exploit the locally-rich benthic ecosystem, while diel patterns in pelagic waters in summer are probably a response to strong vertical migration patterns within the copepod-based pelagic food web. Behavioral flexibility that permits such switching between different feeding strategies may have important consequences regarding the potential for southern elephant seals to adapt to variability or systematic changes in their environment resulting from climate change.
Keywords: Bouvetøya; Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

Holocene Antarctic climate variability from ice and marine sediment cores: insights on ocean-atmosphere interaction - Divine, Dmitry; Koç, Nalân; Isaksson, Elisabeth; Nielsen, Simon H; Crosta, Xavier; Godtliebsen, Fred (Quaternary Science Reviews, 2010)
Holocene climate variability in the southeast Atlantic sector of the Southern Ocean and Antarctic is assessed and quantified through integration of available marine sediment core and Antarctic ice core data. We use summer sea surface temperature (SSST) and sea ice presence (SIP) reconstructions from two marine sediment cores recovered north (50 °S) and south (53.2 °S) of the present day Antarctic Polar Front (APF), as well as an atmospheric temperature and sea ice proxy from the EPICA ice core from Dronning Maud Land (EDML). We find reasonably good agreement in the timing of climate evolution in the analyzed series. Almost all records show a gradual glacial-to-Holocene climate transition, interrupted by the Antarctic cold reversal around 13 000 cal yr BP, and early Holocene climatic optimum (HCO) at about 11 000 cal yr BP. During the early HCO, the seasonal ice cover retreats to south of 53 °S; it then readvances in the course of the mid- to late Holocene. The maximum winter sea ice edge position during the recent 10 000 years varied mainly within 51–53 °S, with sporadic growth to north of 50 °S, a position similar to that during the last glacial. The onset of the Neoglacial period after ca 4000 yr BP is associated with a steepening of the SSST gradient between the marine core sites, strengthening of the westerlies and cooling in the inland ice sheet. The agreement in timing between elevated SSST during the early HCO and decreased deuterium excess in EDML and other ice cores from different locations in the East Antarctic suggests that the retreat of sea ice during the early HCO and weakening of the APF was a general feature of the East Antarctic climate during that time.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; glasiologi; holocene; iskjerner; klimaendringer; oseanografi; paleoklimatologi

A New Approach for Exploring Ice Sheets and Sub-Ice Geology - Eisen, Olaf; Hofstede, Coen; Miller, Heinrich; Kristoffersen, Yngve; Blenkner, Rick; Lambrecht, Astrid; Mayer, Christoph (Eos Transactions American Geophysical Union, 2010)
Keywords: Antarktis; geofysikk; geologi; innlandsis; seismologi

Hva skjedde med vågehvalen i Antarktis? - Fujise, Yoshihiro; Hatanaka, Hiroshi; Ohsumi, Seiji (Ottar, 2010)
Jakten på de store bardehvalene i antarktiske farvann startet på begynnelsen av 1900-tallet og reduserte bestandene sterkt. Vågehvalen ble mindre utsatt for fangst og fikk kanskje en fordel da de større konkurrentene forsvant? Det japanske forskningsprogrammet JARPA har studert endringer i det marine økosystemet i Antarktis.
Keywords: Sørishavet; kval; marin biologi; økosystemer

Whalers' wives in Vestfold, Norway during the pelagic period - Garmel, Hanne (Whaling and History III : papers presented at a symposium in Sandefjord on the 18th and 19th of June 2009, 2010)
Keywords: Norge; Sørishavet; hvalfangst; kulturhistorie; pelagisk

Polarskipet Antarctics stolte historie. Del 2 - Goldberg, Fred (Polarboken, 2010)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie; logistikk

Intraspecific differences in the diet of Antarctic fur seals at Nyrøysa, Bouvetøya - Hofmeyr, Greg; Bester, Marthán; Kirkman, Stephen; Lydersen, Christian; Kovacs, Kit (Polar Biology, 2010)
Intraspecific differences in the diets of many species of pinnipeds are to be expected in view of the great differences in morphology, life history and foraging behaviour between the sexes of many species. We examined the diet of the Antarctic fur seal population at Bouvetoya, Southern Ocean, to assess intersexual differences. This was made possible by the analysis of prey remains extracted from scats and regurgitations collected in areas used primarily by one or the other sex. The results indicate that both males and females feed primarily on Antarctic krill Euphausia superba with several species of fish and squid being taken, likely opportunistically given their prevalence. Significant differences were identified in the frequency of occurrence of otoliths in scats and the percentage numerical abundance of the major fish prey species in the diet. Adult males ate a smaller quantity of fish overall, but ate significantly more of the larger fish species. The greater diving capabilities of males and the fact that they are not limited in the extent of their foraging area by having to return regularly to feed dependant offspring may play a role in the differences found between the diets of males and females. Additionally, females might be more selective, favouring myctophids because they are richer in energy than krill. The absence of major differences in the diet between the sexes at this location is likely due to the high overall abundance of prey at Bouvetoya.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; sjøpattedyr

Cruising for krill in the Southern Ocean with G.O. Sars - Iversen, Svein A (Red.); Myklevoll, Sigmund (Red.); Mæstad, Kjartan (Red.); Nøttestad, Leif (Red.) (Institute of Marine Research, 2010)
Keywords: Sørishavet; ekspedisjoner; euphausiacea; forskning; krill; marin biologi; marine økosystemer; plankton; raudåte

Antarctic pioneers : the voyage of the Belgica 1879-99 - Kløver, Geir O (Red.) (The Fram Museum, 2010)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; Sydpolen; ekspedisjoner; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

An 860 km surface mass-balance profile on the East Antarctic plateau derived by GPR - Müller, Karsten; Sinisalo, Anna; Anschütz, Helgard; Hamran, Svein-Erik; Hagen, Jon-Ove; McConnell, Joseph R; Pasteris, Daniel R (Annals of Glaciology, 2010)
Snow accumulation and its variability on the East Antarctic plateau are poorly understood due to sparse and regionally confined measurements. We present a 5.3 GHz (C-band) ground-penetrating radar (GPR) profile with a total length of 860 km recovered during the joint Norwegian–US International Polar Year traverse 2007/08. Mean surface mass balance (SMB) over the last 200 years was derived from the GPR data by identifying the volcanic deposition of the Tambora eruption in 1815. It varies between 9.1 and 37.7 kg m−2 a−1 over the profile, with a mean of 23.7 kg m−2 a−1 and a standard deviation of 4.7 kg m−2 a−1. The 200 year SMB estimated is significantly lower than most of the SMB estimates over shorter time periods in this region. This can be partly explained by a SMB minimum in the vicinity of the ice divide. However, it is more likely that a recent increase in SMB observed by several studies is largely responsible for the observed discrepancy.
Keywords: Antarktis; Dronning Maud Land; glasiologi

Land and sea-ice properties in Antarctica: bridging the gap between the ground and satellite measurements in the western Ross Sea region - Rack, Wolfgang; Langhorne, Pat; Haas, Christian; Clavano, Wendy; Gough, Alex; Kruetzmann, Nikolai; Pinchin, James; Riger-Kusk, Mette (Ice and climate news, 2010)
Keywords: Antarktis; Sørishavet; glasiologi; havis; isshelf

Who owns the history of whaling? The norwegian whaling industry and the writing of modern whaling history - Ringstad, Jan Erik (Whaling and History III : papers presented at a symposium in Sandefjord on the 18th and 19th of June 2009, 2010)
Keywords: Norge; Sørishavet; hvalfangst; kulturhistorie; pelagisk

A frozen field of dreams : science, strategy, and the Antarctic in Norway, Sweden, and the British empire, 1912-1952 : a dissertation submitted to the Department of History and the Committee on graduate studies of Stanford University in partial fulfillment of the requirements for the degree of Doctor of Philosophy - Roberts, Peder (Peder William Chellew Roberts, 2010)
Keywords: Antarktis; Norge; historie; norske ekspedisjoner; politikk

Antarktistraktatens effekt på norsk politikk 1959-2009: fra polarimperium på sparebluss til nye utfordringer - og ny giv? - Skagestad, Odd Gunnar (Norsk militært tidsskrift, 2010)
Keywords: Antarktis; politikk

Roald Amundsen: Conqueror of the South Pole - Thyvold, Hans Olav (Font forl., 2010)
ROALD AMUNDSEN (1872-1928), norsk oppdager, polfarer og nasjonalhelt. Det første mennesket som fant og seilte gjennom Nordvestpassasjen, og førstemann til å sette fot på Sydpolen. Norges nasjonalarv er en serie gjennomillustrerte bøker som presenterer våre viktigste og mest kjente nasjonale ikoner. De enkeltstående bøkene tar for seg betydelige skikkelser innenfor kunst og litteratur, vitenskap, idrett og samfunnsliv, men også landets mange naturperler, samt sentrale historiske epoker og kulturuttrykk. Hver for seg gir bøkene en oppdatert innføring for lesere som vil gjøre seg bedre kjent med et gitt tema.
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Genetic identification of Southern Ocean octopod samples using mtCOI - Undheim, Eivind Andreas Baste; Norman, Janette Ann; Thoen, Hanne Halkinrud; Fry, Bryan Grieg (Comptes Rendus. Biologies, 2010)
East Antarctic octopods were identified by sequencing mtCOI and using four analytical approaches: Neighbor-joining by Kimura-2-Parameter-based distances, character-based, BLAST, and Bayesian Inference of Phylogeny. Although the distance-based analytical approaches identified a high proportion of the sequences (99.5% to genus and 88.1% to species level), these results are undermined by the absence of a clear gap between intra-and interspecific variation. The character-based approach gave highly conflicting results compared to the distance-based methods and failed to identify apomorphic characters for many of the species. While a DNA independent approach is necessary for validation of the method comparisons, crude morphological observations give early support to the distance-based results and indicate extensive range expansions of several species compared to previous studies. Furthermore, the use of distance-based phylogenetic methods nevertheless group specimens into plausible species clades that are highly useful in non-taxonomical or non-systematic studies. (C) 2010 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Sørishavet; blekksprut; genetikk; marin biologi; taksonomi

The whaling expedition of the Ulysses, 1937-1938 - Walsh, Quentin R; Capelotti, P J (red.) (University Press of Florida, 2010)
Keywords: Sørishavet; ekspedisjoner; historie; hvalbåter; hvalfangstindustri; hvalindustri; kulturantropologi; norske; sjøfolk; sjømenn

Continental shelf submission of Norway : in respect of Bouvetøya and Dronning Maud Land : executive summary (Oljedirektoratet, 2009)
Keywords: Bouvetøya; Dronning Maud Land; internasjonal; jus; kontinentalsokkel; politikk

Belgicaekspedisjonen 1897-1899 : den første overvintring i Antarktis - Amundsen, Roald; Kløver, Geir O. (Red.) (Frammuseet, 2009)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; Sydpolen; dagbok; ekspedisjoner; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

East Antarctic snow accumulation changes - Anschütz, Helgard; Isaksson, Elisabeth; Winther, Jan-Gunnar; Müller, Karsten; Albert, Mary (Polar Research in Tromsø, 2009)
Keywords: Antarktis; glasiologi

Time budgets and at-sea behaviour of lactating female Antarctic fur seals Arctocephalus gazella at Bouvetøya - Biuw, Martin; Krafft, Bjørn A.; Hofmeyr, G. J. Greg; Lydersen, Christian; Kovacs, Kit M. (Marine ecology. Progress series, 2009)
We present the first data on attendance patterns, at-sea movements and diving behaviour of Antarctic fur seals breeding at Bouvetøya (Bouvet Island), Southern Ocean. While other colonies have been extensively studied, this remote and second largest global population remains relatively unknown. Time depth recorders and satellite relay data loggers were deployed on breeding females during the 2000–2001 and 2001–2002 summers. Attendance and foraging patterns were similar to those observed at colonies in the Scotia Sea region where Antarctic krill is the predominant prey. Early to mid-lactation trips ranged within ~100 km of the island, usually towards the west. The dominant direction shifted later in the season and the range also increased markedly to a peak between early February and early March. Solar elevation influenced arrivals and departures from the island, with most departures occurring around sunset. Diurnal variations in diving behaviour were consistent with the vertical migration of krill. Diving frequency was higher at night and diving effort peaked around morning twilight. Afternoon deep diving was common, suggesting that females might target dense daytime krill aggregations between the photic zone and the thermocline. Trip durations increased throughout early to mid-lactation, peaking in late January to early March, before again decreasing towards the end of lactation. Our results illustrate the substantial variability, both between individuals and within individuals over time, that is likely to reflect variations in prey distribution and in the growth requirements of pups. Such variations need to be taken into account when estimating habitat use and resource utilisation in marine top predators.
Keywords: Bouvetøya; krill; marin biologi; pelsseler; plankton; satellittsendere; zoologi; økologi

Biologging in the Global Ocean Observing System - Boehme, Lars; Kovacs, Kit M; Lydersen, Christian; Nøst, Ole Anders; Biuw, Martin; Charrassin, Jean-Benoît; Roquet, Fabien; Guinet, Christophe; Meredith, Michael; Nichols, K; Thorpe, Sally; Costa, Daniel; et al. (Proceedings of Ocean Obs 09: Sustained ocean observations and information for society, Venice, Italy, European Space Agency, 2009)
Miniature electronic data recorders and transmitters have revolutionized the way we study animals over the past decades, particularly marine animals at sea. But, very recently, animal-borne instruments have also been designed and implemented that provide in situ hydrographic data from parts of the oceans where little or no other data are currently available (even from beneath the ice in polar regions). Ocean data is delivered from animal-borne instruments via satellites in near real-time, which would enrich the Global Ocean Observing System if animal-borne instruments were deployed systematically. In the last 10 years, studies involving more than 10 countries (Australia, Brazil, Canada, France, Germany, Greenland, Norway, South Africa, UK, USA) have demonstrated how highly accurate oceanographic sensors, integrated into standard animal, biologging instruments, can provide data of equal or better quality than XBT/XCTD data. Here, we present some of the pioneering studies and demonstrate that we now have enough information for many marine species to predict where they will go – within reasonable limits. Thus, we can direct sampling effort to particularly interesting and productive regions and maximize data return. In the future, biologging could certainly play an important part in the Global Ocean Observing System, by providing complementary data to more traditional sampling technologies - especially in the high latitudes. This paper will make a core contribution to the Plenary Sessions 4A, 4B and 5A and will be relevant to 2A, 2B and 3A.
Keywords: Bouvetøya; Sørishavet; biologging; marin biologi; oseanografi

New insights into southern ocean physical and biological processes revealed by instrumented elephant seals - Charrassin, Jean-Benoît; Roquet, Fabien; Park, Young-Hyang; Bailleul, Frédéric; Guinet, Christophe; Meredith, Michael; Nicholls, K; Thorpe, Sally; McDonald, Birgitte; Costa, Daniel; Tremblay, Yann; Goebel, Michael; et al. (Proceedings of Ocean Obs 09: Sustained ocean observations and information for society, Venice, Italy, European Space Agency, 2009)
In recent years, the international “Southern Elephant seals as Oceanographic Samplers” (SEaOS) project has deployed miniaturized conductivity-temperature-depth satellite-relayed data loggers (CTD-SRDL) on elephant seals 1) to study their winter foraging ecology in relation to oceanographic conditions, and 2) to collect hydrographic data from polar regions, which are otherwise sparsely sampled. We summarize here the main results that have been published in both science components since 2003/2004. Instrumented southern elephant seals visit different regions within the Southern Ocean (frontal zones, continental shelf, and/or ice covered areas) and forage in a variety of different water masses (e.g. Circumpolar Deep Water upwelling regions, High Salinity Shelf Water), depending on their geographic distribution. Adult females and juvenile males from Kerguelen Is. forage pelagically in frontal zones of the Southern Indian Ocean, while adult males forage benthically over the Kerguelen Plateau and the Antarctic Continental Shelf, with the two groups feeding at different trophic levels as shown by stable isotopes analysis. Oceanographic studies using the data collected from the seals have, to date, concentrated on circumpolar and regional studies of the Antarctic Circumpolar Current (ACC) circulation. The temperature and salinity profiles documented by elephant seals at high latitudes, including below sea ice, have permitted quasi-circumpolar mapping of the southernmost fronts of the ACC. By merging conventional data and the high temporal and spatial resolution data collected by seal-borne SRDLs, it has been possible to describe precisely 1) the large-scale features of the ACC in the South Atlantic and its variability; 2) the circulation pattern over the Kerguelen plateau, revealing that the poorly known Fawn Trough concentrates an important proportion of the ACC flow in that region. Seals that foraged in ice covered areas have made eulerian time series available that have allowed for the estimation of sea ice formation rates, a parameter that is otherwise difficult to obtain, while also providing a unique description of the wintertime ocean circulation over the central Weddell Sea continental shelf. Finally, we present the first data collected by a newly-developed fluorescence sensor that as been embedded in the regular CTD-SRDL and deployed on elephant seals at Kerguelen. The fluorometer data obtained have offered the first synoptic view of the 3 dimensional distribution of temperature, salinity and fluorescence over a vast sector of the Southern Indian Ocean, allowing us to describe both vertical and horizontal variations in chlorophyll. This paper will make a core contribution to the Plenary Sessions 2C, 3A and 4A, and will be relevant to 2A and 2B.
Keywords: Bouvetøya; Sørishavet; marin biologi; marin zoologi; oseanografi

Pan-African granitoid magmatism in Central Dronning Maud land caused by delamination? - Kleinhanns, Ilka; Jacobs, Joachim; Roland, N W ([Geological Society of America], 2009)
Keywords: Dronning Maud Land; geologi

Cold recall: reflections of a polar explorer - Kløver, Geir O (Fram Museum, 2009)
Keywords: Antarktis; ekspedisjoner; historie

Den norsk-brittisk- svenska expeditionens okända sidor 1949-1952 - Lewander, Lisbeth (Ymer, 2009)
Discusses scientific work of 1949-52 Norwegian-British-Swedish Antarctic expedition, with particular reference to international tensions of early Cold War period.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Forutsetninger for Antarktistraktaten: hva var Norges linje? - Skagestad, Odd Gunnar (Norsk militært tidsskrift, 2009)
Keywords: Antarktis; politikk

Suverenitet, jurisdiksjon og samarbeid: Antarktistraktaten – forutsetninger og innhold - Skagestad, Odd Gunnar (Norsk statsvitenskapelig tidsskrift, 2009)
Keywords: Antarktis; jus; politikk

[Im kyank’y vorpes beverrayin hetazotogh] - Amundsen, Roald; Movsisyaně, Suren (Toner, 2008)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

Historical Polar bases - preservation and management - Barr, Susan (red.); Chaplin, Paul (red.) (ICOMOS International Polar Heritage Committee, 2008)
Keywords: Antarktis; forskningsstasjoner; kulturminnevern; kulturvern; polarområdene

Predicting the fate of ice shelves - Galton-Fenzi, Benjamin K (Ice and climate news, 2008)
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

Den Norske Antarktis-ekspedisjonen, 1956-60: Norway Station - Henriksen, Hans Martin (Polarboken, 2008)
Keywords: Dronning Maud Land; ekspedisjoner; geofysikk; historie; logistikk

Polar exploration - Huntford, Roland (Two planks and a passion : the dramatic history of skiing, 2008)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; skihistorie; utstyr

Early Palaeozoic orogenic collapse and voluminous late-tectonic magmatism in Dronning Maud Land and Mozambique: insights into the partially delaminated orogenic root of the East African–Antarctic Orogen? - Jacobs, Joachim; Bingen, Bernard; Thomas, Robert J; Bauer, Wilfried; Wingate, Michael T D; Feitio, Paulino (Geological Society, London, Special Publications, 2008)
Keywords: Dronning Maud Land; geokjemi; geokronologi; geologi; tektonikk

Antarctic ices shelves in a changing climate - Jenkins, Adrian (Ice and climate news, 2008)
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

In situ measurements of snow surface roughness using a laser profiler - Lacroix, Pascal; Legrésy, B; Langley, Kirsty; Hamran, Svein Erik; Kohler, Jack; Roques, S; Rémy, F; Dechambre, M (Journal of Glaciology, 2008)
The snow surface roughness at centimetre and millimetre scales is an important parameter related to wind transport, snowdrifts, snowfall, snowmelt and snow grain size. Knowledge of the snow surface roughness is also of high interest for analyzing the signal from radar sensors such as SAR, altimeters and scatterometers. Unfortunately, this parameter has seldom been measured over snow surfaces. The techniques used to measure the roughness of other surfaces, such as agricultural or sand soils, are difficult to implement in polar regions because of the harsh climatic conditions. In this paper we develop a device based on a laser profiler coupled with a GPS receiver on board a snowmobile. This instrumentation was tested successfully in midre Lovénbreen, Svalbard, in April 2006. It allowed us to generate profiles of 3 km sections of the snow-covered glacier surface. Because of the motion of the snowmobile, the roughness signal is mixed with the snowmobile signal. We use a distance/frequency analysis (the empirical mode decomposition) to filter the signal. This method allows us to recover the snow surface structures of wavelengths between 4 and 50 cm with amplitudes of >1 mm. Finally, the roughness parameters of snow surfaces are retrieved. The snow surface roughness is found to be dependent on the scales of the observations. The retrieved RMS of the height distribution is found to vary between 0.5 and 9.2 mm, and the correlation length is found to be between 0.6 and 46 cm. This range of measurements is particularly well adapted to the analysis of GHz radar response on snow surfaces.
Keywords: Antarktis; glasiologi; teknologi

Radar Scattering Zones across Dronning Maud Land, East Antarctica - Müller, Karsten; Albert, Mary; Hamran, Svein Erik; Hagen, Jon Ove Methlie (International Glaciological Society, 2008)
Keywords: Dronning Maud Land; geovitenskap; glasiologi

Tilbake til Sydpolen - Munch, Anita Thorolvsen (Polaråret: et magasin om det internasjonale polaråret 2007-2008, 2008)
I fjor vinter skapte norske og amerikanske forskere og teknikere historie da de la ut på en tre måneders ekspedisjon til Sydpolen. Snart vender de tilbake for nye tre måneder. Fire store innsjøer under isen venter på å bli undersøkt.
Keywords: Dronning Maud Land; ekspedisjoner; glasiologi

Helse og helbred sønnafor verden. Litt om legetjenester og helsetilstand blant hvalfangere - Ringstad, Jan Erik (Mdisinhistorie til sjøs, 2008)
Keywords: Sørishavet; helsevesenet; hvalfangere; hvalfangst; pelagisk

Rødt gull i Sørishavet - Stephansen, Susanne Moen (Polaråret: et magasin om det internasjonale polaråret 2007-2008, 2008)
En rekelignende skapning i Sørishavet er Kjell Inge Røkkes nye yndling. Den kan nemlig brukes i alt fra slankemidler til fiskefôr. Men vet vi nok om krill til å slippe trålerne løs? Forskningsskipet G.O. Sars har vært på tokt for å finne u mer.
Keywords: Sørishavet; krill; marin biologi

Land-fast ice variation during the past five decades: Lützow-Holm Bay, Antarctica - Ushio, Shuki (Ice and climate news, 2008)
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

Vår glemte polarhelt : Carsten Borchgrevink og Southern Cross-ekspedisjonen 1898-1900 - Vogt, David (Aschehoug, 2008)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Nordmenn; Ole Must; Per Savio; Southern Cross; Sydpolen; biografier; ekspedisjonen; ekspedisjoner; oppdagelsesreiser; polarforskning; polarområdene; samisk

Klimagåten Antarktis - Winther, Jan-Gunnar (Gyldendal, 2008)
Keywords: Antarktis; IPY; Sydpolen; ekspedisjoner; internasjonale polarår; isbreer; klimaendringer; klimatologi; polarforskning

Norge i Antarktis : fra erobring til moderne forskning - Winther, Jan-Gunnar; Andersen, Rolf Trolle; Basberg, Bjørn L; Bomann-Larsen, Tor; Haugland, Jan Erling; Njåstad, Birgit; Orheim, Olav; Tveraa, Torkild; Monsen, Oddbjørn (Schibsted, 2008)
Keywords: Antarktis; Norge; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Norway in the Antarctic : from conquest to modern science - Winther, Jan-Gunnar; Tveraabak, Jacob; Andersen, Rolf Trolle; Basberg, Bjørn L; Bomann-Larsen, Tor; Haugland, Jan Erling; Njåstad, Birgit; Orheim, Olav; Monsen, Oddbjørn; Goldman, Helle V (Schibsted, 2008)
Keywords: Antarktis; Norge; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Seasonal forecast of Antarctic sea ice and beyond - Yuan, Xiaojun (Ice and climate news, 2008)
Keywords: Sørishavet; glasiologi; havis

Antarktis : en eventyrlig seilas - Aasheim, Stein P; Nævra, Arne (NRK aktivum, 2007)
Keywords: Antarktis; dyreliv; geografi; historie; hvalfangst; populærvitenskap; reisebeskrivelser

Pan-African granulites of central Dronning Maud Land and Mozambique: a comparison within the East-African-Antarctic orogen - Engvik, Ane K; Elvevold, Synnøve; Jacobs, Joachim; Tveten, E; de Azevedo, S; Njange, F (Antarctica - a keystone in a changing world: online proceedings for the 10th International Symposium on Antarctic Earth Sciences, 2007)
Granulite-facies metamorphism is extensively reported in Late Neoproterozoic/Early Palaeozoic time during formation of the East-African-Antarctic orogen (EAAO). Metamorphic data acquired from the Pan-African orogen of central Dronning Maud Land (cDML) are compared with data from northern Mozambique. The metamorphic rocks of cDML are characterised by Opx±Grt-bearing gneisses and Sil+Kfs-bearing metapelites which indicate medium-P granulite-facies metamorphism. Peak conditions, which are estimated to 800-900ºC at pressures up to 1.0 GPa, were followed by near-isothermal decompression during late Pan-African extension and exhumation. Granulite-facies lithologies are widespread in northern Mozambique, and Grt+Cpx-bearing assemblages show that high-P granulitefacies conditions with PT reaching 1.55 GPa and 900ºC were reached during the Pan-African orogeny. Garnet is replaced by symplectites of Pl+Opx+Mag indicating isothermal decompression, and the subsequent formation of Pl+amphibole-coronas suggests cooling into amphibolite facies. It is concluded that high-T metamorphism was pervasive in EAAO in Late Neoproterozoic/Early Paleozoic time, strongly overprinting evidences of earlier metamorphic assemblages.
Keywords: Dronning Maud Land; geologi

På nåde over Antarktis : verdens lengste skitur : 4804 km - Gjeldnes, Rune (SEAL Adventure, 2007)
Keywords: Antarktis; geografi; oppdagelsesreiser; polarekspedisjoner; reiser; reiseskildringer

Den Norske Antarktisekspedisjonen 1956-60 : Norway Station (Fimbul) - Henriksen, Hans-Martin (2007)
Keywords: Antarktistraktaten 1959; Den norske antarktisekspedisjonen 1956–1960; Det internasjonale geofysiske år 1957/58; Dronning Maud Land; IGY 1957-58; NAX; geologi; glasiologi; jordmagnetiske målinger; kartlegging; meteorologi; overvintring; tidevannsmålinger

Henrik Bull, the Antarctic Exploration Committee and the first confirmed landing on the Antarctic continent - McConville, Andrew (Polar Record, 2007)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; D/S Antarctic; Henrik Johan Bull; Kapp Adare; Leonard Kristensen; Rosshavet; Victoria Land; ekspedisjoner; forskning; første landgang; oppdagelsesreiser

The Southern Ice Ocean Model Intercomparison Project (SIOMIP) - O'Farrell, Siobhan (Ice and climate news, 2007)
Keywords: Sørishavet; forskning; glasiologi; havis

Hval og politikk : hvalfangstnæringens rolle i utformingen av den norske hvalfangstpolitikken på 1950-tallet - Thorsen, Eivind; Kolle, Nils (Universitetet i Bergen, 2007)
Siste halvdel av 1950-tallet var en viktig periode i norsk hvalfangst. Norge, som tidligere hadde vært den dominerende hvalfangstnasjonen, var som resultat av hard konkurranse kommet på defensiven i forhold til de andre hvalfangstnasjonene. Den høye hvaloljeprisen, som blant annet var forårsaket av Europas fettbehov i kjølvannet av den andre verdenskrig, resulterte i at nye nasjoner etter krigen engasjerte seg i hvalfangst. For å sikre seg en størst mulig andel av totalkvoten ønsket Sovjetunionen og Japan nå å foreta en kraftig utbygging av sine fangstflåter, noe som ville gjøre situasjonen enda vanskeligere for den norske hvalfangstnæringen. Det var av største viktighet at denne ekspansjonen ble stoppet, siden dette spørsmålet i norske hvalfangstkretser ble oppfattet som et være eller ikke være for norsk hvalfangst. De norske hvalfangstselskapene startet derfor en kampanje for å få regjeringen til å stanse de to landenes utbyggingsplaner. Mitt hovedfokus i denne oppgaven vil være å belyse hvalfangstnæringens rolle i utformingen av den norske hvalfangstpolitikken på 1950-tallet. For å kunne gi et svar på dette spørsmålet har jeg tatt for meg to av hvalfangstpolitikkens viktigste saker dette tiåret. Den første dreier seg om den nevnte kampen for å stanse Sovjetunionens og Japans ekspansjonsplaner, mens den andre dreier seg om kampen for en ordning med nasjonale kvoter. En studie av disse to sakene gir også innsyn i næringen som helhet. I tillegg til å kartlegge hvalfangstnæringens politiske innflytelse vil det også være viktig å gi en fremstilling av utviklingen innen hvalfangstreguleringen i denne perioden, altså siste halvdel av 1950-tallet. Med begrepet norsk hvalfangstpolitikk, mener jeg den politikken regjeringen utformet og som blant annet ble presentert på de årlige møtene i Den internasjonale hvalfangskommisjonen (IWC). For å kunne gi et godt svar på problemstillingen er det nødvendig å besvare flere underliggende spørsmål. Hvalfangstselskapene organiserte seg tidlig gjennom dannelsen av Norges Hvalfangstforbund. Dette var en organisasjon som kjempet for at hvalfangstredernes interesser ble ivaretatt. Hvalfangstrederne var i tillegg representert i Hvalrådet. Dette var et statlig organ som hadde en rådgivende funksjon i regjeringens utarbeidelse av den norske hvalfangstpolitikken. Følgende spørsmål blir derfor viktige i mitt arbeid: Hvilken rolle spilte Norges Hvalfangstforbund i utformingen av den norske hvalfangstpolitikken? Hvordan opererte næringens representanter for å få gjennomslag for sine interesser i Hvalrådet? Det vil også være nødvendig å kartlegge sammenhengen mellom Hvalrådet og regjeringen. I hvilken grad var Hvalrådets uttalelser utslagsgivende for den endelige norske hvalfangstpolitikken? Bortsett fra tiden da Norge stod utenfor Den internasjonale hvalfangstkonvensjonen, sendte landet hvert år en delegasjon til kommisjonens årlige møter. Det vil være viktig å undersøke i hvilken grad næringen var representert i disse delegasjonene. Møtte den norske delegasjonen med bundet mandat, eller hadde den en viss frihet til å forhandle? Mot slutten av oppgaven ønsker jeg å se komparativt på hvalfangstnæringens politiske innflytelse i forhold til landbruket og fiskerinæringen i den samme perioden. Oppnådde hvalfangstnæringen større politisk innflytelse sammenliknet med disse næringene, og hva skyldtes i tilfelle dette?
Keywords: Sørishavet; historie; hvalfangst; pelagisk; politikk

Det første forskningstoktet til Antarktis - Tofte, Kari Østervold (Polaråret: et magasin om det internasjonale polaråret 2007-2008, 2007)
Keywords: Sørishavet; forskning; marin biologi

Widerøe kartlegger i Antarktis - Widerøe, Turi (Perspektiv, 2007)
Keywords: Antarktis; Dronning Maud Land; Lars Christensen; Norvegia ekspedisjoner; flyhistorie; hvalfangst; kartlegging

International Workshop on Antarctic Sea-Ice Thickness, Hobart, Tasmania, 5-7 July 2006 - Worby, Tony; Ackley, Steve (Ice and climate news, 2007)
Keywords: Sørishavet; glasiologi; havis; konferanser

Antarctic sea ice processes and climate program, The International Polar Year - Ackley, Steve; Worby, Tony (Ice and climate news, 2006)
Keywords: Sørishavet; forskning; glasiologi; havis; klima

One-to-one coupling of glacial climate variability in Greenland and Antarctica - Barbante, Carlo et al. (Nature, 2006)
Precise knowledge of the phase relationship between climate changes in the two hemispheres is a key for understanding the Earth’s climate dynamics. For the last glacial period, ice core studies1,2 have revealed strong coupling of the largest millennial-scale warm events in Antarctica with the longest Dansgaard–Oeschger events in Greenland3,4,5 through the Atlantic meridional overturning circulation6,7,8. It has been unclear, however, whether the shorter Dansgaard–Oeschger events have counterparts in the shorter and less prominent Antarctic temperature variations, and whether these events are linked by the same mechanism. Here we present a glacial climate record derived from an ice core from Dronning Maud Land, Antarctica, which represents South Atlantic climate at a resolution comparable with the Greenland ice core records. After methane synchronization with an ice core from North Greenland9, the oxygen isotope record from the Dronning Maud Land ice core shows a one-to-one coupling between all Antarctic warm events and Greenland Dansgaard–Oeschger events by the bipolar seesaw6. The amplitude of the Antarctic warm events is found to be linearly dependent on the duration of the concurrent stadial in the North, suggesting that they all result from a similar reduction in the meridional overturning circulation.
Keywords: Dronning Maud Land; glasiologi; klima

In the wake of Tønnessen and Johnsen : trends in whaling history research after 1970 - Basberg, Bjørn L. (Whaling and History II : new perspectives, 2006)
In 1970 the fourth and final volume of Arne Odd Johnsen and Joh. N. Tønnessens’s Den moderne hvalfangsts historie was published. The work represented a milestone in the writing about the development of the 20th century whaling industry. This paper reviews the literature that has been published in Norway and internationally on the history of modern whaling after Johnsen and Tønnessen, and analyses the focus, trends and direction in the research and writing on whaling history in the period.
Keywords: Antarktis; Sørishavet; hvalfangstindustri; litteratur; pelagisk hvalfangst

The black book of 1913 - a means of disciplining whaling employees - Børresen, Dag Ingemar (Whaling and History II : new perspectives, 2006)
Keywords: Nordmenn; Sørishavet; arbeidsforhold; hvalfangere; pelagisk hvalfangst

the Antarctic buoy program faces new challenges - Haas, Christian (Ice and climate news, 2006)
Keywords: Sørishavet; glasiologi; havis; klima

Whalers and explorers; logistic assistance provided to people whose work, and indeed survival, depended on the whalers - Headland, Robert Keith (Whaling and History II : new perspectives, 2006)
Keywords: Antarktis; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Cetacean feeding, growth and energetics in relation to the marine ecosystem - implications for management? - Lockyer, Christina (Whaling and History II : new perspectives, 2006)
Keywords: Sørishavet; hvaler; hvalfangst; marin biologi; marine økosystemer

Tilbake til Dronning Maud Land, 45 år etter - Martinsen, Jarle R (Polarboken, 2006)
Keywords: Dronning Maud Land; biografi; ekspedisjoner; historie

Høyt mot nord, langt mot sør : reisebrev per satelitt fra Arktis og Antarktis - Michelet, Jon (Oktober, 2006)
Keywords: Antarktis; polarområdene; reiseskildringer

Insignificant change in Antarctic snowfall since the International Geophysical Year - Monaghan, Amdrew J; Bromwich, David H; Fogt, Ryan L; Wang, Sheng-Hung; Mayewski, Paul A; Dixon, Daniel A; Ekaykin, Alexey; Frezzotti, Massimo; Ian Goodwin, Ian; Isaksson, Elisabeth; Kaspari, Susan D; Morgan, Vin I; et al. (Science, 2006)
Keywords: Antarktis; glasiologi

Bjarne Aagaard and his Crusade against Pelagic Whaling in the late 1920s - Ringstad, Jan Erik (Whaling and History II : new perspectives, 2006)
Keywords: Norge; Sørishavet; historie; hvalfangst; pelagisk hvalfangst

"Brategg" og ekspedisjonen til Antarktis i 1947/48: om skuta, ekspedisjonen og deltakrane - Sefland, Magnus (Isflaket, 2006)
Keywords: Peter I. Øy; Sørishavet; båter; ekspedisjoner; historie

Sydpolen - Skog, Cecilie; Sandberg, Sigri (Cecilie Skog og de tre polene, 2006)
Keywords: Antarktis; Sydpolen; Sørpolen; biografi; ekspedisjoner; reiser; reiseskildringer

A review of bipolarity concepts: history and examples from Radiolaria and Medusozoa (Cnidaria) - Stepanjants, Sofia D; Cortese, Giuseppe; Kruglikova, Svetlana Borisovna; Bjørklund, Kjell R (Marine Biology Research, 2006)
Bipolarity, its history and general interpretation are investigated and discussed herein. Apart from the classical view, namely that a bipolar distribution is a peculiar biogeographical phenomenon, we propose that it is ecologically controlled too. This approach was used for bipolarity assessment within the following groups: Phaeodaria, Nassellaria, Spumellaria (Radiolaria) and Medusozoa (Cnidaria). We recognize 46 bipolar radiolarian species and three radiolarian genera. However, although species concepts in radiolarians are relatively stable and well known, the high-rank taxonomy of radiolarians is still not well defined. Caution should therefore be taken in the interpretation of distribution data at a taxonomic level higher than the species. In the Medusozoa, bipolarity is observed for 23 species and 32 genera. The different ways in which bipolarity can develop are discussed under the different groups, but preference has been given to the recent and most probable routes of migration. In our investigation of the bipolarity phenomenon, we reviewed more than 400 articles dealing with taxonomy, ecology and biogeography of the modern fauna in both groups.
Keywords: Sørishavet; marinbiologi; migrasjon; nesledyr; plankton; økologi

Åpning av overvintringsstasjonen Troll - Winther, Jan-Gunnar (Polarboken, 2006)
Keywords: Dronning Maud Land; logistikk

Bipolar patterns of intraspecific competition in bryozoans - Barnes, David K A; Kuklinski, Piotr (Marine Ecology Progress Series, 2005)
Polar shores probably represent the most dynamic and extremely disturbed environments on the globe. Nevertheless intense battles amongst sessile organisms for space are commonplace on hard substrata, mainly between fast-growing pioneer species. In this study we examined spatial interactions in encrusting species at 3 sites within each of 2 high Arctic localities, Horsundfjord (77°N) and Kongsfjord (79°N) in Spitsbergen, and 2 Antarctic localities, Signy Island (60°S) and Adelaide Island (68°S). In both polar regions 1 to 11% of encrusting fauna were involved in intraspecific interactions. Intraspecific competition was common; it usually involved just 1 or 2 pioneer species, mainly ended in tied outcomes, and most variability was at a local scale. The proportion of intraspecific encounters varied considerably at local (km) scales (19 to 99% intraspecific at different sites), reflecting an extremely patchy environment due to ice scour. Most intraspecific encounters resulted in ties (stand-offs) and again most variability was at a local scale. Many intraspecific encounters were constructive, forming large (>1 m3) foliaceous colonies (termed bioconstructions) whose 3D structures can harbour rich biotas. In other colonies intraspecific competition caused crowding and accelerated ovicell production (reproductive activity). Homosyndrome (fusion) was not observed in the Arctic and was rare in the Antarctic, where its frequency differed significantly between competitor identities. We found that the likelihood of meeting conspecifics versus other species and of tied outcomes in encounters was related to the performance of species in interspecific competition: ties were most common, and homosyndrome only occurred in poor competitors. In the context of rapid Arctic and west Antarctic warming and ice-loading of nearshore waters, we predict strongly changing patterns of intraspecific competition. Indeed we suggest that decreased patchiness of intra- versus interspecific competition and decreased levels of intraspecific competition should be strong indicators of increases in surface water ice-loading from ice-sheet collapses. KEYWORDS: Sublittoral · Benthos · Bioconstruction · Climate change · Homosyndrome
Keywords: Sørishavet; bentiske organismer; bryozoa; klimaendringer; marin biologi; miljøendringer; oseanografi; polarområdene

Cryosphere-hydrosphere interactions: Numerical modeling using the regional ocean Modeling System (ROMS) at different scales - Bergamasco, Andrea; Budgell, W. P.; Carniel, Sandro; Sclavo, Mauro (Il Nuovo cimento della Società Italiana di Fisica. C. Geophysics and space physics, 2005)
Conveyor belt circulation controls global climate through heat and water fluxes with atmosphere and from tropical to polar regions and vice versa. This circulation, commonly referred to as thermohaline circulation (THC), seems to have millennium time scale and nowadays-a non-glacial period-appears to be as rather stable. However, concern is raised by the buildup Of CO2 and other greenhouse gases in the atmosphere (IPCC, Third assessment report: Climate Change 2001, A contribution of working group I, II and III to the Third Assessment Report of the Intergovernmental Panel on Climate Change (Cambridge Univ. Press, UK) 2001, http://www.ipcc.ch) as these may affect the THC conveyor paths. Since it is widely recognized that dense-water formation sites act as primary sources in strengthening quasi-stable THC paths (Stommel H., Tellus, 13 (1961) 224), in order to simulate properly the consequences of such scenarios a better understanding of these oceanic processes is needed. To successfully model these processes, air-sea-ice-integrated modelling approaches are often required. Here we focus on two polar regions using the Regional Ocean Modeling System (ROMS). In the first region investigated, the North Atlantic-Arctic, where open-ocean deep convection and open-sea ice formation and dispersion under the intense air-sea interactions are the major engines, we use a new version of the coupled hydrodynamic-ice ROMS model. The second area belongs to the Antarctica region inside the Southern Ocean, where brine rejections during ice formation inside shelf seas origin dense water that, flowing along the continental slope, overflow becoming eventually abyssal waters. Results show how nowadays integrated-modelling tasks have become more and more feasible and effective; numerical simulations dealing with large computational domains or challenging different climate scenarios can be run on multi-processors platforms and on systems like LINUX clusters, made of the same hardware as PCs, and codes have been accordingly modified. This relevant numerical help coming from the computer science can now allow scientists to devote larger attention in the efforts of understanding the deep mechanisms of such complex processes.
Keywords: Sørishavet; geofysikk; klimaendringer; klimamodeller; oseanografi; polarområdene

Polar-Noreg : det kvite eventyret - Elstad, Åsa; Balto, Ann Kristin (bildered.) (Universitetet i Tromsø, 2005)
Keywords: Antarktis; fangst; forskning; historie; oppdagelser; polarområdene; utstillinger

Polar Norway : the white adventure - Elstad, Åsa; Balto, Ann Kristin (bildered.) (Universitetet i Tromsø, 2005)
Keywords: Antarktis; fangst; forskning; historie; oppdagelser; polarområdene; utstillinger

Polarliv og røre : det var nasjonens største, dyreste og mest prestisjetunge svipptur til Antarktis. En historisk markering av polarnasjonen Norge. Så kom isfronten - Engdal, Eskil (Dagens Næringsliv "Magasinet", 2005)
Keywords: Dronning Maud Land; Olav Orheim; Troll forskningsstasjon; polarekspedisjoner

Antarctic surface and subsurface snow and ice melt fluxes - Liston, Glen E.; Winther, Jan-Gunnar (Journal of Climate, 2005)
This paper presents modeled surface and subsurface melt fluxes across near-coastal Antarctica. Simulations were performed using a physical-based energy balance model developed in conjunction with detailed field measurements in a mixed snow and blue-ice area of Dronning Maud Land, Antarctica. The model was combined with a satellite-derived map of Antarctic snow and blue-ice areas, 10 yr (1991–2000) of Antarctic meteorological station data, and a high-resolution meteorological distribution model, to provide daily simulated melt values on a 1-km grid covering Antarctica. Model simulations showed that 11.8% and 21.6% of the Antarctic continent experienced surface and subsurface melt, respectively. In addition, the simulations produced 10-yr averaged subsurface meltwater production fluxes of 316.5 and 57.4 km3 yr−1 for snow-covered and blue-ice areas, respectively. The corresponding figures for surface melt were 46.0 and 2.0 km3 yr−1, respectively, thus demonstrating the dominant role of subsurface over surface meltwater production. In total, computed surface and subsurface meltwater production values equal 31 mm yr−1 if evenly distributed over all of Antarctica. While, at any given location, meltwater production rates were highest in blue-ice areas, total annual Antarctic meltwater production was highest for snow-covered areas due to its larger spatial extent. The simulations also showed higher interannual meltwater variations for surface melt than subsurface melt. Since most of the produced meltwater refreezes near where it was produced, the simulated melt has little effect on the Antarctic mass balance. However, the melt contribution is important for the surface energy balance and in modifying surface and near-surface snow and ice properties such as density and grain size.
Keywords: Antarktis; Dronning Maud Land; glasiologi; klimatologi; meteorologi

Vår sydligste provins: fortellingen om Dronning Maud Land - Skagestad, Odd Gunnar (Nytt norsk tidsskrift, 2005)
Keywords: Dronning Maud Land; historie; politikk

Perturbation of hydrochemical conditions in natural microcosms entombed within Antarctic ice - Tranter, Martyn; Fountain, Andrew G; Fritsen, Christian H; Lyons, W Berry; Priscu, John C; Statham, Peter J; Welch, Kathy A (Ice and climate news, 2005)
Keywords: Antarktis; glasiologi; hydrokjemi

Learning from the Antarctic whaling : report and proceedings - Walløe, Lars; Barthelmess, Klaus; Gambell, Ray; Ohsumi, Seiji; Komatsu, Masayuki (The Institute of Cetacean Research, 2005)
Keywords: Antarktis; Sørishavet; historie; hvalfangstindustri; hvalindustri; pelagisk

Ekspedisjoner og begivenheter - Barr, Susan (Norsk polarhistorie, 2004)
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; oppdagelsesreiser; polarfarere

Cultural heritage in the Arctic and Antarctic regions - Barr, Susan (red.); Chaplin, Paul (red.) (ICOMOS International Polar Heritage Committee, 2004)
Keywords: Antarktis; kulturminnevern; kulturvern; polarområdene

Whalers, explorers and scientists: historical perspectives on the development of the antarctic whaling industry - Basberg, Bjørn L (Antarctic challenges : historical and current perspectives on Otto Nordenskjöld's Antarctic expedition 1901-1903, 2004)
Keywords: Carl Anton Larsen; Norge; Sørishavet; ekspedisjoner; forskning; historie; hvalfangere; hvalfangst; pelagisk; polarområdene

Amundsen og hans aeronauter - Berg, Roald (Norsk polarhistorie, 2004)
Keywords: Antarktis; Norvegia ekspedisjoner; flyging; flyvere; oppdagelsesreiser

Den første norske oljealderen - Elstad, Åsa (Norsk polarhistorie, 2004)
Keywords: Sørishavet; ekspedisjoner; hvalfangstindustri; hvalolje; pelagisk

Polarturisme - Elstad, Åsa (Norsk polarhistorie, 2004)
Keywords: Antarktis; polarområdene; turisme

Ein grådig fangstnasjon? - Elstad, Åsa; Finstad, Bjørn-Petter (Norsk polarhistorie, 2004)
Keywords: Sørishavet; hvalfangstselskaper; hvalindustri; hvalolje; kulturhistorie; pelagisk; politikk; økonomi

Pan-African extension and near-isothermal exhumation of a granulite facies terrain, Dronning Maud Land, Antarctica - Engvik, Ane K.; Elvevold, Synnøve (Geological Magazine, 2004)
The Mühlig-Hofmann- and Filchnerfjella in central Dronning Maud Land, Antarctica, consist of series of granitoid igneous rocks emplaced in granulite and upper amphibolite facies metamorphic rocks. The area has experienced high-temperature metamorphism followed by near-isothermal decompression, partial crustal melting, voluminous magmatism and extensional exhumation during the later phase of the late Neoproterozoic to Cambrian Pan-African event. Remnants of kyanite–garnet–ferritschermakite–rutile assemblages indicate an early higher-pressure metamorphism and crustal overthickening. The gneisses experienced peak granulite facies temperatures of 800–900 °C at intermediate pressures. Breakdown of garnet + sillimanite + spinel-bearing assemblages to cordierite shows subsequent re-equilibration to lower pressures. An E–W foliation dominating the gneisses illustrates transposition of migmatites and leucocratic melts which evolved during the near-isothermal decompression. Occurrence of extensional shear bands and shear zones evolving from the ductile partial melting stage through semiductile towards brittle conditions, shows that the uplift persisted towards brittle crustal conditions under tectonic W/SW-vergent extension. Late-orogenic Pan-African quartz syenites intruded after formation of the main gneiss fabric contain narrow semiductile to brittle shear zones, illustrating that the extensional exhumation continued also after their emplacement. The latest record of the Pan-African event is late-magmatic fluid infiltration around 350–400 °C and 2 kbar. At this stage the Pan-African crust had undergone 15–20 km exhumation from the peak granulite facies conditions. We conclude that the later phase of the Pan-African event in central Dronning Maud Land is characterized by a near-isothermal decompression P–T path and extensional structures indicating tectonic exhumation, which is most likely related to a late-orogenic collapsing phase of the Pan-African orogen.
Keywords: Dronning Maud Land; geologi; petrologi

Polarheltene - minner og monumenter - Eriksen, Anne (Norsk polarhistorie, 2004)
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; polarfarere; polarområdene

The race for the South Pole: Robert Scott and Roald Amundsen (1911-12) - Fleming, Fergus (Off the map : tales of endurance and exploration, 2004)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; oppdagelsesreiser; polareksspedisjoner

Å spise kirsebær med de store - Friedman, Robert Marc (Norsk polarhistorie, 2004)
Keywords: Antarktis; Dronning Maud Land; Norge; Norsk Polarinstitutt; ekspedisjoner; forskning; oppdagelsesreiser

"En æressag for vor nation" - Fulsås, Narve (Norsk polarhistorie, 2004)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; oppdagelsesreiser

Kappløp i gamle spor - Goksøyr, Matti (Norsk polarhistorie, 2004)
Keywords: Antarktis; Nordmenn; ekspedisjoner

Klodens helse - sett fra polene - Hessen, Dag O (Norsk polarhistorie, 2004)
Keywords: Antarktis; Dronning Maud Land; Norge; ekspedisjoner; forskning; internasjonalt samarbeid

Firn accumulation records for the past 1000 years on the basis of dielectric profiling of six cores from Dronning Maud Land, Antarctica - Hofstede, Coen M; Roderik, S W van de Wal; Kaspers, Karsten Adrian; van den Broeke, Michiel R; Karlöf, Lars; Winther, Jan-Gunnar; Isaksson, Elisabeth; Lappegard, Gante; Mulvaney, Robert; Oerter, Hans; Wilhelms, Frank (Journal of Glaciology, 2004)
This paper presents an overview of firn accumulation in Dronning Maud Land (DML), Antarctica, over the past 1000 years. It is based on a chronology established with dated volcanogenic horizons detected by dielectric profiling of six medium-length firn cores. In 1998 the British Antarctic Survey retrieved a medium-length firn core from western DML. During the Nordic EPICA (European Project for Ice Coring in Antarctica) traverse of 2000/01, a 160 m long firn core was drilled in eastern DML. Together with previously published data from four other medium-length ice cores from the area, these cores yield 50 possible volcanogenic horizons. All six firn cores cover a mutual time record until the 29th eruption. This overlapping period represents a period of approximately 1000 years, with mean values ranging between 43 and 71 mm w.e. The cores revealed no significant trend in snow accumulation. Running averages over 50 years, averaged over the six cores, indicate temporal variations of5%. All cores display evidence of a minimum in the mean annual firn accumulation rate around AD 1500 and maxima around AD 1400 and 1800. The mean increase over the early 20th century was the strongest increase, but the absolute accumulation rate was not much higher than around AD 1400. In eastern DML a 13% increase is observed for the second half of the 20th century.
Keywords: Dronning Maud Land; geofysikk; glasiologi; iskjerner; paleoklimatologi

Southern Ocean climate variability - Nielsen, Simon Harder Holm (University of Tromsø and Norwegian Polar Institute, 2004)
Keywords: Sørishavet; havnivå; holocene; klimaendringer

De tre store - Næss, Atle (Norsk polarhistorie, 2004)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser

17th International FRISP Workshop held at the British Antarctic Survey, Cambridge, U.K. on 17th and 18th June 2003 - Smedsrud, Lars H. (Forum for Research into Ice Shelf Processes Report, 2004)
Keywords: Antarktis; Sørishavet; glasiologi; havis

No horizon is so far : two women and their extraordinary journey across Antarctica - Arnesen, Liv; Bancroft, Ann; Dahle, Cheryl (Da Capo Press, 2003)
Keywords: Antarktis; ekspedisjoner; polarekspedisjoner; reiseskildringer

Pionerforskning i Sørishavet. Kappløpet mot Sydpolen - Berg, Kåre; Brenna, Åsta (Polarheltene : norske pionerer i Arktis og Antarktis, 2003)
Keywords: Antarktis; Carl Anton Larsen; Carsten Borchgrevink; Roald Amundsen; Sydpolen; biografier; oppdagelsesreiser; polarekspedisjoner; polarflyving; polarforskning; polarhelter

Pioneering exploration in the Antarctic Ocean. The race for the South Pole - Berg, Kåre; Brenna, Åsta; Aase, Jean (Heroes of the polar wastes : pioneer Norwegian explorers in the Arctic and the Antarctic, 2003)
Keywords: Antarktis; Carl Anton Larsen; Carsten Borchgrevink; Roald Amundsen; Sydpolen; biografier; oppdagelsesreiser; polarekspedisjoner; polarflyving; polarforskning; polarhelter

Storms, ice, and whales : the antarctic adventures of a Dutch artist on a Norwegian whaler - Does, Willem van der (William B. Eerdmans, 2003)
Keywords: Carl Anton Larsen; Norge; Sørishavet; ekspedisjoner; hvalfangere; hvalfangst

Selection of Antarctic personnel - Grant, Iain; Palinkas, Larry; Suedfeld, Peter; Eriksen, Hege; Ursin, Holger (Proceedings of the Tenth Symposium on Antarctic Logistics and Operations, Shanghai, July 15-18 2002, 2003)
Keywords: Antarktis; logistikk; psykologi

Numerical simulation: The Antarctic - Grønås, Sigbjørn; Raustein, Elmer; Heinemann, Guenther (Polar lows : mesoscale weather systems in the polar regions, 2003)
Keywords: Antarktis; atmosfæren; geofysikk; meteorologi

Mitt polarliv : blant forskere, fly og eventyrere i sør og nord - Haugland, Jan Erling (Skyline, 2003)
Keywords: Antarktis; Nordmenn; ekspedisjoner; reiseskildringer

Women and couples in isolated extreme environments: applications for long-duration missions - Leon, Gloria R.; Sandal, Gro Mjeldheim (Acta Astronaut, 2003)
Expedition teams provide a number of analogs relevant to crew selection for long-duration space missions. Three groups were studied that varied in team composition. Group 1 was a two woman international dyad that traversed the Antarctic continent in 97 days. Similarities in problem solving approach, respect for each other's opinions, and a collaborative process of decision making were evident. Group 2 was composed of four women, all from different countries, engaged in a six week trek across Greenland. The most important factors in overcoming interpersonal difficulties and contributing to the successful completion of the expedition were mutual respect and motivation to maintain positive and supportive relationships. Group 3 consisted of three married couples from different countries icelocked on a boat in the High Arctic for a 9 month period. The emotional support of and ability to confide in their partner were extremely important in alleviating interpersonal tensions, and contributed to the generally effective functioning of the group. Women add an element of emotional support and help to other team members that is not as evident in all-male groups. Selection of couples with strong bonds to each other is another paradigm for crew selection for extended missions.
Keywords: Antarktis; polareksspedisjoner; polarforskere; polarområdene; psykologi

Early spring pack ice algae from the Arctic and Antarctic: how different are they? - McMinn, Andrew; Hegseth, Else N (Backhuys, 2003)
Keywords: Antarktis; alger; biodiversitet; biologi; havis; sjøis

Christensen, Lars - Mills, William J (Exploring polar frontiers : a historical encyclopedia, 2003)
Keywords: Antarktis; biografier; ekspedisjoner; hvalfangst; polarhistorie; polfarere

Forecasting of polar lows : aspects of forecasting specific to the Antarctic - Rasmussen, Erik A; Turner, John; Røsting, Bjørn (Polar lows : mesoscale weather systems in the polar regions, 2003)
Keywords: Antarktis; atmosfæren; geofysikk; meteorologi

Validation of AMSR sea-ice products in the Bellinghausen Sea, Antarctica - Steffen, Konrad (Ice and climate news, 2003)
Keywords: Sørishavet; glasiologi; havis; teknologi

Tvers over Antarktis: Bancroft Arnesen Expedition Antarctica 2000-2001 - Arnesen, Liv (Polarboken, 2002)
Keywords: Antarktis; ekspedisjoner

Fluid-rock interactions around pegmatites and aplites in Dronning Maud Land, Antartica - Engvik, Ane; Austrheim, Håkon ([Geoscience Society of Iceland], 2002)
Precambrian granitoid gneisses and Cambrian syenites occur in Mülig-Hofmann- and Filchnerfjella, Dronning Maud Land, Antartica. The nunataks of Dronning Maud land are characterized by alternating dark and light decolourised rocks. This phenomena is observed all along the mountain range for minimum 150 km length and occur in different rock types. The dark parts contain granulite facies mineral assemblages including perthite, plagioclase, orthopyroxene, garnet, biotite and cummingtonite. The light zones contain amphibolite facies minerals typically microcline, amphibole, biotite and titanite. The light zones are restricted to halos around aplite and pegmatite dykes. The widths of the halos range from cm to several meters. In the 800 m high wall of Rakekniven three sets of decolouration zones are observed. Decolouration along dykes is the typically occurrence of the phenomena, however in many places only small remnants of the dark coloured rocks occur and some nunataks are completely decolourised. In mineral scale the feldspars of light rocks are fractured and microveins occur filled by albite and white mica. The veins are irregular but occur in 2-3 main directions. Microstructures are studied towards the central dyke of decolouration zones; fracture density in the feldspars increase, perthite is transformed to microcline and plagioclase recrystallises to small grains of albite and white mica. We interpret the decolouration to be caused by fluid emanated from aplites and pegmatites interacting with the granulites. During the fluid infiltration granulite facies rocks are transformed to amphibolite facies rocks. Fracturing on mineral scale is the important mechanism for transporting fluids out into the wall rock from the dykes. The resulting recrystallisation allows for further fluid transport during breakdown of minerals and production of new grain boundaries. The process is thorough as whole nunataks are affected by the transformation. The frequent distribution of decolouration zones throughout the mountain range indicates a regional importance of the fluid infiltration process.
Keywords: Dronning Maud Land; geologi

Snow grain-size measurements in Antarctica - Gay, Michael; Fily, Michel; Genthon, Christophe; Frezzotti, Massimo; Oerter, Hans; Winther, Jan-Gunnar (Journal of Glaciology, 2002)
Grain-size is an important but not well-known characteristic of snow at the surface of Antarctica. In the past, grain-size has been reported using various methods, the reliability, reproducibility and intercomparability of which is not warranted. In this paper, we present and recommend, depending on available logistical support, three techniques of snow-grain sampling and/or imaging in the field as well as an original digital image-processing method, which we have proved provides reproducible and intercomparable measures of a snow grain-size parameter, the mean convex radius. Results from more than 500 samples and 3000 images of snow grains are presented, which yield a still spatially limited yet unprecedentedly wide picture of near-surface snow grain-size distribution from fieldwork in Antarctica. In particular, except at sites affected by a very particular meteorology, surface grains in the interior of the ice sheet are uniformly small (0.1–0.2 mm). The climate-related increase of grain-size with depth through metamorphism is, as expected, not spatially uniform. Our Antarctic snow grain-size database will continue to grow as field investigations bring new samples, images and measures of snow grain.
Keywords: Antarktis; glasiologi; paleoklimatologi

Spenningssøking i Norsk Antarktis Ekspedisjon 1999-2001 - Gjølme, Egil Galaaen (Norges teknisk-naturvitenskapelige universitet, 2002)
Keywords: Antarktis; ekspedisjoner; psykologi

På store vinger til Dronning Maud Land (DML) - Haugland, Jan Erling (Polarboken, 2002)
Keywords: Dronning Maud Land; ekspedisjoner; logistikk

Pinniped and seabird research at Bouvetøya, 2000/01 : final contract report for the Norwegian Polar Institute - Hofmeyr, Greg; Bester, Marthán (Universty of Pretoria, 2002)
Keywords: Bouvetøya; ekspedisjoner; fugler; pelsseler; pinnipedier; seler; zoologi

Pinniped research at Bouvetøya, 2001/02 : final contract report for the Norwegian Polar Institute - Hofmeyr, Greg; Bester, Marthán (Universty of Pretoria, 2002)
Keywords: Bouvetøya; ekspedisjoner; pelsseler; pinnipedier; seler; zoologi

Glede og motivasjon på Norsk Antarktis ekspedisjon 1999-2001 - Hølen, Jacob Christian (Norges teknisk-naturvitenskapelige universitet, 2002)
Keywords: Antarktis; ekspedisjoner; psykologi

Operasjon pingvin : historien om 7070 støtteving - Jansen, Per Einar (Per Einar Jansen, 2002)
Keywords: Den norske antarktisekspedisjonen 1956–1960; Det internasjonale geofysiske år 1957/58; Dronning Maud Land; IGY 1957-58; NAX; flyging; flyrekognosering; historie; luftfart; luftforsvaret; luftfotografi; polarhistorie

Bouvetøya pinniped monitoring programme: December 1998 - February 1999: final contract report for the Norwegian Polar Institute - Kirkman, Stephen; Bester, Marthán ([Universty of Pretoria], 2002)
Keywords: Bouvetøya; ekspedisjoner; pelsseler; pinnipedier; seler; zoologi

Antarctica - Sale, Richard (Polar reaches : the history of Arctic and Antarctic exploration, 2002)
Keywords: Antarktis; Sydpol; Sydpolsekspedisjonen; ekspedisjoner; fangst; forskning; hvalfangere; oppdagelsesreiser; polarområdene

Antarctica - Sale, Richard (To the ends of the Earth : the history of Polar exploration, 2002)
This text provides an insight into the early history of the Polar regions, and tells the stories of Man's first exploration of the Arctic and Antarctic, and subsequent expeditions. The history of individual Polar expeditions has been told many times, but usually only as personal accounts of individual adventures. This misses the overall context of polar exploration - why the British depended on ponies, or plant-eating animals (on the only continent where plants don't grow), why Franklin's men perished when the local Eskimos were eking out an existence around them (and reporting Franklin's demise), and why the Scandinavians were always better than anybody else. The first map of Antarctica was produced in 1556 - the Vikings visited the Arctic 1,000 years before. In 2001, the US Base at the South Pole is manned 365 days a year. The book tells the whole story of how the two last wildernesses, at either end of the world, were discovered, conquered and tamed.
Keywords: Antarktis; Belgica ekspedisjon; Carsten Egeberg Borchgrevink; Nordmenn; Norge; Roald Amundsen; Southern Cross; Sydpolsekspedisjonen; ekspedisjonen; historie; hvalfangst; oppdagelsesreiser; pelagisk; polareksspedisjoner

Mindre is i et varmere Antarktis - Smedsrud, Lars Henrik; Rolstad, Cecilie (Cicerone, 2002)
Keywords: Antarktis; global oppvarming; issmelting; klimaendringer; populærvitenskap

The protocol on environmental protection to the Antarctic Treaty: a ten-year review - Vidas, Davor (Yearbook of international co-operation on environment and development, 2002)
Keywords: Antarktis; jus; miljøvern

Antarctic Treaty: Report of the Norwegian antarctic inspection under article VII of the Antarctic Treaty ([Justis- og beredskapsdepartementet], 2001)
Article VII of the Antarctic Treaty entitles each Consultative Party to designate observers who shall have the right to carry out unannounced on-spot inspections. The purpose of these inspections is to promote the objectives of and ensure compliance with the provisions of the Antarctic Treaty and the easures adopted under it. The observers shall be accorded complete freedom of access at any time to all areas of Antarctica, including all stations within those areas, as well as vessels and aircrafts at points of embarkation and disembarkation. Article 14 of the Protocol on Environmental Protection to the Antarctic Treaty commit the Consultative Parties to undertake inspections under Article VII of the Antarctic Treaty in order to promote the protection of the Antarctic environment and dependent and associated ecosystems, and to ensure compliance with the Environmental Protocol.
Keywords: Antarktis; Norge; forskningsstasjoner

Research on Antarctic affairs at the FNI (Nansen news, 2001)
Keywords: Antarktis; forskning

Energetisk elektronnedbør over Antarktis - Åsnes, Arne (Universitetet i Bergen, 2001)
Keywords: Antarktis; fysikk

Trollbundet : en liten saga om en lang tur - Bø, Sindre (Commentum forl., 2001)
Keywords: Antarktis; polarekspedisjoner; polarområdene; reiser; reiseskildringer

Med hvalbåten "Silva" ved Syd-Shetland: om originaltegningen og opphavsmannen til jagebrua - Børresen, Dag Ingemar (Ambra : Sandefjordmuseene årbok, 2001)
Keywords: Sørishavet; hvalfangst; teknologi

Electron density variations in the upper D region at high latitudes according to in situ measurements - Danilov, Alexey; Smirnova, N.V.; Vanina-Dart, Liudmila; Blix, Tom Arild; Thrane, Eivind (Geomagnetism and Aeronomy, 2001)
A large set of rocket measurements of the electron concentration [e] in the upper D region at four rocket sites (Molodezhnaya (Antarctic), Heiss Island (Arctic), Syowa (Antarctic), and Andoya/Kiruna (Arctic)) is considered. The dependence of [e] on the solar zenith angle X and geomagnetic activity index ∑Kp is analyzed. It has been shown that, the spread in [e] values reaches two orders of magnitude at any assigned value of χ. Nevertheless, it is possible to draw a lower envelope for the entire set of points and to obtain the [e] variation with χ in undisturbed conditions. In an analysis of the envelopes, it is seen that a corpuscular ionization source (presumably, electrons with an energy of above 40 keV) exists in the nonsunlit D region even in quiet conditions. An analysis of the electron concentration dependence on the daily sum of ∑Kp indices (∑Kp) shows that, at all heights considered, increases [e] with increasing ∑Kp to a certain boundary value ∑Kp and then remains either constant (with a rather wide spread in the data) or even decreases. This saturation effect may be caused by the auroral oval equatorward motion. As a result of this motion the site position may change: it may move toward the boundary between the auroral oval and polar cap or even be within the latter. The slope k of the [e] variation plotted versus ∑Kp at different χ is considered. It is shown that k grows with increasing χ and is maximal at χ> 100°.
Keywords: Antarktis; geofysikk; geomagnetiske stormer; ionosfæren; meteorologi; polarområdene

A local geoid in Dronning Maud Land - The NARE 96/97 Geoid - Eiken, Trond; Omang, Ove Christian Dahl; Øvstedal, Ola (IGeS Bulletin, 2001)
The main purpose of the present paper is to estimate the orthometric height of the Global Positioning System (GPS)-station at Troll, Dronning Maud Land, Antarctica. Located at approximately 1300 m above sea level Troll has been connected to the Geodetic Infrastructure forAntarctica (GIANT)-network, but it’s orthometric height remains undetermined. A local geoid has been determined based on gravity-, tidal- and GPS-observations and available gravity anomalies. Information about the ice-thickness has been included in the terrain model. Based on tidal measurements the mean sea level was determined in Jutulgryta, a rift zone in the Fimbulisen ice shelf. Several gravity- and GPS-stations were measured between the two points (Jutulgryta andTroll), a distance of approximately 100 km.
Keywords: Dronning Maud Land; NARE 1996/97; Troll forskningsstasjon; geodesi; kartlegging

Mumifiserte seler fra Dronning Maud Land, Antarktis - Gjertz, Ian; Wiig, Øystein (Fauna, 2001)
Keywords: Dronning Maud Land; dyr; seler; zoologi

Pesca: the history of Compañia Argentina de Pesca Sociedad Anónima of Buenos Aires: an account of the pioneer modern whaling and sealing company in the Antarctic - Hart, Ian B (Aidan Ellis, 2001)
Keywords: Antarktis; Carl Anton Larsen; fiskeindustri; hvalfangere; hvalfangst; hvalfangstindustri; hvalfangstnæring; hvalindustri; pelagisk; økonomi

A high-altitude snow chemistry record from Amundsenisen, Dronning Maud Land, Antarctica - Isaksson, Elisabeth; Karlén, Wibjörn; Mayewski, Paul; Twickler, Mark; Whitlow, Sallie (Journal of Glaciology, 2001)
In this paper a detailed record of major ions from a 20 m deep firn core from Amundsenisen, western Dronning Maud Land, Antarctica, is presented. The core was drilled at 75° S, 2° E (2900 m a.s.l.) during austral summer 1991/92. The following ions were measured at 3 cm resolution: Na+, Mg2+, Ca2+, Cl−, NO3−, S04 2− and CH3SO3H (MSA). The core was dated back to 1865 using a combination of chemical records and volcanic reference horizons. The volcanic eruptions identified in this core are Mount Ngauruhoe, New Zealand (1974–75), Mount Agung, Indonesia (1963), Azul, Argentina (1932), and a broad peak that corresponds in time toTarawera, New Zealand (1886), Falcon Island, South Shetlands, Southern Ocean (1885), and Krakatau, Indonesia (1883). There are no trends in any of the ion records, but the annual to decadal changes are large. The mean concentrations of the measured ions are in agreement with those from other high-altitude cores from the Antarctic plateau. At this core site there may be a correspondence between peaks in the MSA record and major El Niño–Southern Oscillation events.
Keywords: Dronning Maud Land; fysisk geografi; glasiologi; iskjerner; kjemi; meteorologi

Klimavariasjoner gjennom de siste 45 000 14C år i Weddellhavet, Antarktis - Larsen, Anne Marit Løland (Universitetet i Bergen, 2001)
Keywords: Sørishavet; Weddellhavet; maringeologi; paleoklimatologi; sedimenter

Metal dynamics in an Antarctic food chain - Nygård, Torgeir; Lie, Elisabeth; Røv, Nils; Steinnes, Eiliv (Marine Pollution Bulletin, 2001)
The concentrations of copper, zinc, cadmium, selenium and mercury were determined in eggs, muscle, liver, kidney and stomach content of nestlings and adults of the Antarctic petrel, Thalassoica antarctica, and its predator, the south polar skua, Chataracta maccormicki, from Svarthamaren, Dronning Maud Land, Antarctica. The dominant food of the petrels is krill, Euphausia superba. The results show relatively high levels of cadmium in krill, which is assumed to be the main reason for the high levels of cadmium in petrels and skuas. Cadmium is almost absent in eggs, but accumulates very rapidly with age in nestlings. The copper concentrations in livers of nestling petrels reach very high levels during growth. This may be seen in connection with physiological development processes. Mercury seems to be accumulated with age and between trophic levels. Among the nestlings, the mercury levels decrease with increasing age, which may be accomplished by the excretion of mercury through the growth of feathers and as a dilution effect during growth. Selenium and mercury are inversely correlated in nestlings. The levels of zinc were similar for different nestling stages and between nestlings and adults in skuas and petrels.
Keywords: Dronning Maud Land; antarktispetrell; forurensning; fugler; krill; miljøgifter; næringskjede; ornitologi

Lichens of Antarctica and South Georgia : a guide to their identification and ecology - Øvstedal, Dag Olav; Smith, Ronald Lewis (Cambridge University Press, 2001)
Keywords: Antarktis; botanikk; lav; planter

Blue-ice areas in Antarctica derived from NOAA AVHRR satellite data - Winther, Jan-Gunnar; Jespersen, Martin Nørman; Liston, Glen E. (Journal of Glaciology, 2001)
We have mapped Antarctic blue-ice areas using the U.S. National Oceanic and Atmospheric Administration (NOAA) Advanced Very High Resolution Radiometer (AVHRR) Antarctica cloud-free image mosaic established by the United States Geological Survey. The mosaic consists of 38 scenes acquired from 1980 to 1994. Our results show that approximately 60 000 km2 of blue ice exist for each of the two main types of blue ice: “melt-induced” and “wind-induced”. Normally, the former type is located on slopes in coastal areas where climate conditions (i.e. persistent winds and temperature), together with favourable surface orientation, sustain conditions for surface and near surface melt. The latter blue-ice category occurs near mountains or on outlet glaciers, often at higher elevations, where persistent winds erode snow away year-round, and combined with sublimation creates areas of net ablation. Furthermore, we have identified an additional area of 121 000 km2 as having potential for blue ice. However, in these areas features such as mixed pixels, glazed snow surfaces, crevasses and/or shadows make interpretation more uncertain. In conclusion, a conservative estimate of Antarctic blue-ice area coverage by this method is found to be 120 000 km2 (∼0.8% of the Antarctic continent), with a potential maximum of 241 000 km2 (∼1.6% of the Antarctic continent).
Keywords: Antarktis; Dronning Maud Land; blåis; fjernmåling; glasiologi; satellite bilder; teknologi

South through the Pole 1997-98 - Arnesen, Liv (Polarboken, 2000)
Keywords: Antarktis; ekspedisjoner

IFIX - inductive data acquisition system: system for sub ice shelf data acquisition - Lothe, Torleif (Filchner-Ronne Ice Shelf Programme. Report, 2000)
Keywords: Antarktis; Sørishavet; forskning; teknologi

Oceanographic observations south of Berkner Island: preliminary results - Nicholls, Keith W; Østerhus, Svein; Makinson, Keith; Johnson, Mark (Filchner-Ronne Ice Shelf Programme. Report, 2000)
Keywords: Sørishavet; oseanografi

Norway: Implementing the Protocol on Environmental Protection - Njåstad, Birgit (Implementing the Environmental Protection Regime for the Antarctic, 2000)
Keywords: Antarktis; Antarktistraktaten; miljøprotokollen; miljøvern

The Committee for Environmental Protection: Its Establishment, Operation and Role within the Antarctic Treaty System - Orheim, Olav (Implementing the Environmental Protection Regime for the Antarctic, 2000)
Keywords: Antarktis; miljø; miljøkonsekvensanalyser; miljøpåvirkning

The large-scale dynamics of Jutulstraumen drainage basin, East Antarctica - Rolstad, Cecilie Eie (Unipub forlag, 2000)
Keywords: Antarktis; Sydpolen; geografi; glasiologi

Large-scale force budget of an outlet glacier: Jutulstraumen, Dronning Maud Land, East Antarctica - Rolstad, Cecilie; Whillans, Ian M.; Hagen, Jon Ove; Isaksson, Elisabeth (Annals of Glaciology, 2000)
A large-scale force budget was applied using a combination of remote-sensing and field data from Jutulstraumen, Dronning Maud Land, Antarctica. In the grounded area, more than 95 % of ice flow is balanced by basal friction. In a partly floating section near the grounding-line area, on average lateral drag provides 38% of resistance to flow. Measurement uncertainties were propagated through the calculation of forces. The accuracies of strain rates derived from satellite data (Landsat thematic mapper) were found adequate to calculate meaningful force-balance terms. For the floating section, where lateral forces contribute to controlling flow, the main contribution to errors in the force budget is uncertainty in the rate factor for the flow law of ice. For grounded sections, the uncertainty in ice thickness, as measured by ground-penetrating radar, contributes more or less equally to errors in the force budget as does that in the rate factor.
Keywords: Dronning Maud Land; fjernanalyse; glasiologi; isstrøm; satellittbilder

Henryk Johan Bull (1893-1895). Carsten E. Borchgrevink (1898-1900). Roald Amundsen (1910-1912) - Rosove, Michael H (Let heroes speak : Antarctic explorers, 1772-1922, 2000)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Henrik Johan Bull; Roald Amundsen; Sydpolen; biografier; oppdagelsesreiser; polarekspedisjoner

Coping in Antarctica: is it possible to generalize results across settings? - Sandal, Gro Mjeldheim (Aviation Space and Environmental Medicine, 2000)
Background: To gain knowledge about psychological issues in space, data have been collected from groups in isolated and confined settings on Earth. This study examines the possibility of generalizing psychological findings across such environments. HYPOTHESIS: Psychological reactions among personnel in different Antarctic environments show similar time patterns. Antarctic personnel differ in personality from submariners to crews confined in hyperbaric chambers to military recruits. METHOD: Psychological reactions were evaluated by the Revised Antarctic Questionnaire. The Personality Characteristic Inventory was used to measure personality. RESULTS: Personnel stationed on a ship (n = 19) showed high coping during the whole mission, whereas personnel on land bases (n = 18) showed a marked decline around the third quarter. Reduced coping in the land-based groups was associated with stress from interpersonal relationships. Compared with submariners (n = 54) and hyperbaric chamber crews (n = 20), Antarctic personnel scored lower on competitiveness and higher on achievement striving. CONCLUSIONS: Similarities in physical, individual and group characteristics should be considered before extrapolating psychological findings across settings.
Keywords: Antarktis; overvintring; polarekspedisjoner; polarforskere; polarområdene; psykologi

Determination of Q1, an unknown organochlorine contaminant, in human milk, Antarctic air, and further environmental samples - Vetter, Walter; Alder, Lutz; Kallenborn, Roland; Schlabach, Martin (Environmental Pollution, 2000)
Q1, an organochlorine component with the molecular formula C(9)H(3)Cl(7)N(2) and of unknown origin was recently identified in seal blubber samples from the Namibian coast (southwest of Africa) and the Antarctic. In these samples, Q1 was more abundant than PCBs and on the level of DDT residues. Furthermore, Q1 was more abundant in seals from the Antarctic than the Arctic. To prove this assumption, gas chromatography-electron-capture negative ion mass spectrometry (GC/ECNI-MS), which is sensitive and selective for Q1, allowed for screening of traces of Q1 even in samples with particularly high levels of other organochlorine contaminants. Q1 was isolated by high-performance liquid chromatography (HPLC) from a skua liver sample. A 1:1 mixture with trans-nonachlor in electron-capture detectors (ECDs) was used to determine the relative response factor with ECNI-MS. The ECNI-MS response of Q1 turned out to be 4.5 times higher than that of trans-nonachlor in an ECD. With GC/ECNI-MS in the selected ion-monitoring mode, four Antarctic and four Arctic air samples were investigated for the presence of Q1. In the Antarctic air samples, Q1 levels ranged from 0.7 to 0.9 fg/m(3). In Arctic air samples, however, Q1 was below the detection limit (<0.06 fg/m(3) or 60 ag/m(3)). We also report on high Q1 levels in selected human milk samples (12-230 microg/kg lipid) and, therefore, suggested that the unknown Q1 is an environmental compound whose origin and distribution should be investigated in detail. Our data confirm that Q1 is a bioaccumulative natural organochlorine product. Detection of a highly chlorinated natural organochlorine compound in air and human milk is novel.
Keywords: Antarktis; forurensning; kromatografi; miljøgifter; miljøovervåking; toksikologi

Implementing the environmental protection regime for the antarctic - Vidas ed., Davor (Kluwer, 2000)
Keywords: Antarktis; jus; miljøvern

Protecting the polar marine environment : law and policy for pollution prevention - Vidas, Davor (ed.) (Cambridge University Press, 2000)
Keywords: Antarktis; forurensning; hav; miljørett; miljøvern; polarområdene; skadeforebygge

The ATS on the Web: Introducing Modem Information Technology in Antarctic Affairs - Vidas, Davor; Njåstad, Birgit (Implementing the Environmental Protection Regime for the Antarctic, 2000)
Keywords: Antarktis; Antarktistraktaten; miljøprotokollen; miljøvern